La naissance du quartier de la Poudrière (1) - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Armes; Femmes; Guerre; Verdun

Les 50 ans de l'effondrement de la rue Wellington - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Rues; Transport en commun; Verdun

Le mystère de Crawford Park-(Partie 3) - Voisine, John (Les Argoulets, 2024)
Keywords: Logement; Quartiers; Verdun

L'avenue du Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2024)
issued: 2024-21-00
Keywords: Magasins; Mont-Royal (rue); Plateau Mont-Royal; Tremblay; Michel

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Destination: demain - Barrieau, Pierre; Richard, Geneviève (Continuité, 2024)
issued: 2024-21-00
Keywords: Transport en commun

La Belle Centenaire - Bolduc, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Logement; Patrimoine; Sault-au-Récollet

Le parc Molson et ses abords - Bouchard-Dupont, Maude (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Parcs; Rosemont

Sur le chemin des tanks - Boucley, Pierre (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Armes; Guerre; Usines Angus

John Elsdale Molson contre le chemin de fer Grand Tronc - Bur, Justin (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Chemins de fer; Grand Tronc; Rosemont

Le rôle des économistes et des influences transnationales dans les réformes économiques de la première phase de la Révolution tranquille (1960-1966) : un tour d'horizon - Carlos, Jean-Philippe (La Révolution tranquille entre l’ici et l’ailleurs, 2024)
Keywords: Indépendantisme; Nationalisme

L'église Saint-Arsène il était une foi... - Desautels, Stéphanie (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont; Églises

La maison du jardinier/The gardener's house - Design NFA inc. (Héritage Dorval, 2024)
Keywords: Chemins de fer; Clubs; Dorval; Jardins; Patrimoine

L'histoire du chemin du Roy, XVIII-XXᵉ siècles : étude historique d'une route, d'un symbole, d'un récit - Fortin-Dupuis, Simon (Université Laval, 2024)
Keywords: Routes

Nos autoroutes, un patrimoine? - Gagnon, Maurice (Continuité, 2024)
issued: 2024-21-00
Keywords: Autoroutes; Patrimoine

Un aperçu des résidents du Parc Amherst 1892-1921 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Locataires; Logement; Rosemont

Le 1035 rue de Bellechasse: une coopérative trentenaire dans un bâtiment centenaire - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Coopérative d'habitation de Montréal; Rosemont

La Halte de La Visitation - Goulet, Patrick (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: La Visitation (église); Patrimoine; Sault-au-Récollet

« Dear Richard...send us a few buffalo tongue »: Donald Smith's Fur Trade Contacts and Peronal Credit Networks - Hamon, Max (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Autochtones; Bourgeoisie; Chemins de fer; Femmes; Fourrure; Golden Square Mile

Des oeuvres qui transportent - Labrosse, Benoîte (Continuité, 2024)
issued: 2024-23-00
Keywords: Transport en commun

Métro, direction conservation - Lévesque, Jonathan; Senese, Manuela (Continuité, 2024)
issued: 2024-21-00
Keywords: Patrimoine; Transport en commun

Le mouvement Desjardins à Verdun, une histoire centenaire - Lussier, Pierre (Les Argoulets, 2024)
Keywords: Caisses populaires; Verdun

Max Aitken in Montreal: Financial Innovation and Creative Destruction in the Laurier Boom - Marchildon, Gregory P. (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Banques; Bourgeoisie; Golden Square Mile

« Others of more entreprise »: Thomas Morland and the Formation of Montreal Rolling Mills, 1858-1868 - Mathieu, Jean-Philip (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Montreal Rolling Mills; Quartiers

Une victorienne bien cachée! - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Famille; Logement; Sault-au-Récollet

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

La ligne de métro No.3 (rouge) à Dorval/Line 3 (red) in Dorval - Raymond, Jean-Pierre (Héritage Dorval, 2024)
Keywords: Dorval; Transport en commun

Dans la rue. Une histoire du FRAPRU et des luttes pour le logement au Québec - Saillant, François (Écosociété, 2024)
Keywords: Groupes populaires; Logement

The Changing of the Guard: Bartlett McLennean, Roy Wolvin, and the Leveraged Buyout of the Montreal Transportation Compagny, 1903-1921 - Salmon, M. Stephen (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Navigation

Rails vers Dorval/Rails to Dorval - Smith, Douglas N.W (Héritage Dorval, 2024)
Keywords: Banlieue; Chemins de fer; Grand Tronc

Le bungalow, un témoin de l'histoire d'Anjou - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-21-00
Keywords: Anjou; Banlieue

Tramway à Montréal-1861 à 1959 - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-22-00
Keywords: Montreal Street Railway Company; Tramways

Westmount Station: Canadian Pacific history and future visioning - Hanna, David B. (The Westmount Historian, 2023)
Keywords: Canadien Pacifique; Commémoration; Gares

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

De Lorimier 1895-1909 (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-24-00
Keywords: Chaussure; De Lorimier (village); Parcs; Usines Angus

Le Plateau industriel (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-22-00
Keywords: Alimentation; Chaussure; Grèves; Plateau Mont-Royal (arrondissement); Travail; Vêtements

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

L'histoire des boissons gazeuses Corona - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Alimentation; Verdun

Fertile Pairings: A Cultural History of the Early Commercial Mandate of the Société des alcools du Québec (1968–1978) - Duchesne, Marie-Joëlle (Journal of the Canadian Historical Association/Revue de la société historique du Canada, 2023)
Keywords: Alcool; Tempérance

Les coûts de la vie : genre, citoyenneté et politique des prix à Montréal dans les années 1940 - Fahrni, Magda (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Alimentation; Femmes; Prix; Épicerie

Ucal-Henri Dandurand et la pratique des ventes de sociétés immobilières à Montréal, au tournant du XXe siècle - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2023)
Keywords: Publicité

DOHERTY, CHARLES JOSEPH - Glassford, Larry A. (Dictionnaire biographique du Canada, 2023)

L’héritage contrasté de l’âge d’or du pétrole : histoire et évolution des paysages de l’est de Montréal - Hatton-Proulx, Clarence; Mercure Jolette, Frédéric; Van Neste, Sophie L. (Recherches sociographiques, 2023)
Keywords: Anjou; Montréal-Est; Paysages; Pollution; Pétrole

Les entrepreneurs libertariens au Québec : une croissance continue depuis 1995 - Laberge, Thomas (Bulletin d'histoire politique, 2023)
issued: 2023-21-00
Keywords: Idéologies; Libéralisme

“La Grève de la fierté”: Resisting Deindustrialization in Montréal’s Garment Industry, 1977–1983 - Laframboise, Lauren (Labour / Le Travail, 2023)
issued: 2023-23-00
Keywords: Femmes; Grèves; International Ladies' Garment Workers' Union; Vêtements

La propriété en conflit: Justice et droit du logement à Montréal (1941-1980) - Mercier, Ian (Université du Québec à Trois-Rivières, 2023)
Keywords: Droit; Logement; Tribunaux

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

Fabriquer la tradition canadienne-française : le tabac canadien et la construction de l’identité canadienne-française, 1880-1950 - Rudy, Jarrett (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Tabac

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
issued: 2023-21-00
Keywords: Juifs; Saint-Laurent (rue)

Une brève histoire des caisses populaires dans Rosemont-La Petite-Patrie - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2023)
Keywords: Banques; Caisses populaires; Rosemont

Des origines à la Dépression. Quartier Crawford Park- (Partie 2) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

Une mesure d'origine britannique. Les barrières à péage à Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
issued: 2023-21-00
Keywords: Outremont; Routes

Un arrondissement parsemé d'anciennes carrières - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Parcs; Rosemont

La carrière Rhéaume 1909-1937 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Rosemont

Saint-André-Apôtre. La vie communautaire s’organise - Ménard, Céline (Au fil d’ABC / SHAC, Société d’histoire d’Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Caisses populaires; Groupes populaires

Le travail traditionnel dans les carrières de calcaire de Montréal: un prélude à la carrière Rhéaume - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Artisans; Carrière; Charretiers; Travail

Les premières institutions bancaires de la rue Masson - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Banque Canadienne nationale; Banque d'Hochelaga; Banque de Montréal; Banques

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Crawford; Alexander

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

Dictionnaire historique des gens du livre au Québec - Aubin, Paul; Luneau, Marie-Pier; Vincent, Josée (Les Presses de l'Université de Montréal, 2022)
Keywords: Imprimerie

Archambault au service des Québécois depuis 1896 - Bergeron, Normand (Il était une fois...Montréal-Nord, 2022)
issued: 2022-21-00
Keywords: Commerce de détail; Librairie; Magasins; Musique

Le travail du métal à Montréal au XVIIe siècle. Des métiers '' d’avenir '' ? - Blouin, Sonia (2022)
issued: 2022-24-00
Keywords: Armuriers; Fer et acier

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Translators: _:n461 Translators: _:n62043
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n199 Translators: _:n62269
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

TRUDEAU, JOSEPH-CHARLES-ÉMILE - English, John (Dictionnaire biographique du Canada, 2022)

Le pont Royal-Albert, 1875-1876: histoire d'une bérézina sur fond de rivalités ferroviaires - Fougères, Dany (Revue d'histoire de l'Amérique française, 2022)
issued: 2022-24-00
Keywords: Chemins de fer; Grand Tronc; Ponts

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels

Travailleuses anonymes et modernité énergétique. L’industrie électrique et gazière et l’économie domestique à Montréal, 1904-1959 - Hatton-Proulx, Clarence (Revue d'histoire de l'Amérique française, 2022)
issued: 2022-24-00
Keywords: Femmes; Montreal Light; Heat and Power; Travail; École ménagère; Électricité

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Les Pharmacies Leduc, 100 ans d'existence - Leduc, Guy (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Pharmacie

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

Les phares de Dorval et d'autres aides à la navigation sur le Lac Saint-Louis/The Dorval Lightouse and other navigation aids on Lake St. Louis - Nieuwendyk, Dick (Héritage Dorval, 2022)
Keywords: Navigation; Saint-Louis (lac)

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman; William; Photographie; Publicité

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Two Commemorative Pitchers, or the End of an Era. 1846. Repeal of the Corn Laws - Pothier, Louise (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n188 Translators: _:n62336
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-23-00
Keywords: Logement

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n38 Translators: _:n62447
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Sir Hormisdas Laporte: Homme d'affaires et maire de Montréal (1850-1934) - Saint-Pierre, Marjolaine (Septentrion, 2022)
Keywords: Maires; Philanthropie

Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Prohibition-Brasserie Chapman-Microbrasseries - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2022)
Keywords: Alcool; Brasserie; Prohibition

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-23-00
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Les caisses populaires d'Ahuntsic-Cartierville dans l'après-guerre, témoins d'une urbanisation accélérée - Linteau, Paul-André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 10
Keywords: Ahuntsic; Arrondissements; Caisses populaires; Cartierville

Vivre dans une boîte à chaussure - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 10
Keywords: Logement

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Number: 112
Keywords: Famille; Logement; Mariage

De la reconquête économique du Canada français à la " république coopérative " du Québec: l’idéal de coopération économique chez François-Albert Angers (1937-1976) - Carlos, Jean-Philippe (Recherches sociographiques, 2021)
issued: 2021-09/2021-12
Keywords: Courants intellectuels; Idéologies

La revue Mon Mariage: vendre du rêve (1948-1951) - Luneau, Marie-Pier; Warren, Jean-Philippe (Recherches sociographiques, 2021)
issued: 2021-05/2021-09
Keywords: Mariage

L'énigmatique maison de ferme de la 23e avenue - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Logement

Le docteur Ananie-Joseph Millier, un notable rosemontois méconnu - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Logement; Médecine; Quartiers; Rosemont

Alexander Crawford, le notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Crawford; Alexander

L’action des promoteurs immobiliers dans le processus de gentrification du Sud-Ouest de Montréal - Gaudreau, Louis; Houle, Marc-André; Fauveaud, Gabriel (Recherches sociographiques, 2021)
issued: 2021-01/2021-04
Keywords: Arrondissements; Gentrification; Le Sud-Ouest; Logement

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Enfin chez soi! - Archambault-Malouin, Diane; Beauchamp, Maurice; St-Marseille, Michel (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Coopérative d'habitation de Montréal; La Familiale; Logement; Sault-au-Récollet

DeSerres, une entreprise montréalaise - Bergeron, Normand (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Magasins

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

La boulangerie Le Pain moderne canadien de Montréal. Les promesses du pain industriel - Burgess, Joanne (Cap-aux-Diamants, 2021)
issued: 2021-23-00
Keywords: Alimentation; Boulangerie

History, Memory, and Struggle in Saint-Henri, Montreal - Burrill, Fred (Université Concordia, 2021)
Keywords: Saint-Henri; Travail

BRAINERD, THOMAS CHALMERS - Cloutier, J.-Roger (Dictionnaire biographique du Canada, 2021)

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Pour la mémoire collective. Rien n'est jamais perdu - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

Les premières maisons shoebox montréalaises de Rosemont et de Villeray - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2021)
issued: 2021-23-00
Keywords: Quartiers; Rosemont; Villages; Villeray

Les minoteries du canal de Lachine - Gelly, Alain (Cap-aux-Diamants, 2021)
issued: 2021-23-00
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie flour Mills

Petites et grandes boulangeries. La fabrication du pain dans le quartier Centre-Sud de Montréal - Giroux, Éric (Cap-aux-Diamants, 2021)
issued: 2021-23-00
Keywords: Alimentation; Boulangerie; Centre-sud (quartier)

Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle) - Guay, Élyse; Nadon, Rachel (Les Presses de l'Université de Montréal, 2021)
Keywords: Cité Libre; Dérives (revue); Femmes; Fugues (revue); Féminisme; Humour; Les Têtes de Pioche (journal); Nationalisme; Parti Pris; Patrimoine; Traduction

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 2
Keywords: Famille; Logement; Quartiers; Rosemont

Rodolphe Forget. Un financier québécois (1861-1919) - Harvey, Christian (Éditions Charlevoix, 2021)
Keywords: Bourse; Hommes d'affaires; Montreal Light; Heat and Power; Électricité

Ateliers à louer, le " phalanstère " d'Alfred Laliberté - Lacroix, Laurier (Les Cahiers des Dix, 2021)
Number: 75
Keywords: Laliberté; Alfred; Locataires; Logement; Peinture; Sculpture

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Produits Familex: de l'usine à votre porte - Landreville, Julie (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Commerce de détail; Pharmacie; Produits pharmaceutiques

Économie de la réputation commerciale. Une histoire du crédit marchand à Montréal au 19e siècle - Lapalme, Alexandre (Université de Montréal, 2021)

COHEN, LYON - Lapidus, Steven (Dictionnaire biographique du Canada, 2021)

The Making of Habitat 67. A Tense Pas de Deux between Moshe Safdie and August Komendant - Legault, Réjean (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Number: 1
Keywords: Béton; Expositions; Logement

DOUGALL, JOHN REDPATH - MacLeod, Roderick (Dictionnaire biographique du Canada, 2021)

SISCOE, STANLEY EDWARD - Momryk, Myron (Dictionnaire biographique du Canada, 2021)

Hartland St. Clair MacDougall. Un résident notable de Dorval/Hartland St. Clair MacDougall. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2021)
Keywords: Bourse; Dorval

De la barge aux usines: les mécanismes de déchargement du charbon au canal de Lachine - Paquet, Lucie (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Lachine (canal); Montreal Rolling Mills

Deux pichets commémoratifs d'un moment marquant. 1846. L'abolition des Corn Laws - Pothier, Louise (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

Enjeux politiques de la frontière entre salubrité et insalubrité dans l'habitation montréalaise des années 1930 - Racette, Jean-Christophe (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-22-00/2021-23-00
Keywords: Crise; Logement; Pauvreté

GRAVEL, LUDGER - Roberts, David (Dictionnaire biographique du Canada, 2021)

Pour les femmes, par les femmes : une histoire entrepreneuriale de la presse féminine québécoise au tournant du XXe siècle - Rocher-Lewis, Delphine (Université du Québec à Montréal, 2021)
Keywords: Barry; Robertine; Bélanger; Georgina (De Montreuil; Gaétane / Bélanger; Georgine); Femmes; Journalistes; Marchand-Dandurand; Joséphine

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Les hommes d'affaires francophones et les défis de l'après-guerre: la chambre de commerce de Montréal (1943-1953) - Sarra-Bournet, Michel (Entre corporatisme et libéralisme. Le patronat québécois dans l’après-guerre, 2021)
Keywords: Chambre de commerce; Hommes d'affaires

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

D’abord, prendre en mains son panier d’épicerie - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 8
Keywords: Alimentation; Chaurès-Louard; Berthe; La Familiale; Logement; Épicerie

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
issued: 2020-24-00
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Saveur café (Mémoire vivante, 2020)
issued: 2020-24-00
Keywords: Alimentation; Cafés; Restaurant; Épicerie

Square Saint-Louis: Lieu mythique (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
issued: 2020-21-00/2020-22-00
Keywords: Librairie; Miron; Gaston; Monuments; Nelligan; Émile; Places publiques; Poésie; Squares; École littéraire de Montréal; Écrivains

Berthe Chaurès-Louard, une femme engagée qui a laissé des traces dans notre communauté - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 7
Keywords: Alimentation; Chaurès-Louard; Berthe; La Familiale

Saveur café: À l'origine du café de Gérard Van Houtte - Bizier, Hélène-Andrée (Mémoire vivante, 2020)
issued: 2020-24-00
Keywords: Alimentation; Cafés; Restaurant; Épicerie

DUMONT, GEORGES-ALMA (Dictionnaire biographique du Canada, 2020)

CARLI, ALEXANDRE - Carlevaris, Anna Maria (Dictionnaire biographique du Canada, 2020)

La Brasserie Dow. Tome 2: La chute - Charlebois, Paul-Yvon; Daignault, Sylvain (Les Éditions GID, 2020)
Keywords: Brasserie; Dow (brasserie)

"L’enseignement universitaire canadien-français mis au service du Canada français": l’université selon les hommes d’affaires canadiens-français de Montréal, 1949-1960 - Colleret, Maxime (Bulletin d'histoire politique, 2020)
issued: 2020-22-00
Keywords: Chambre de commerce; Hommes d'affaires; Nationalisme

"[L']utilisateur du bataillon de jeunes Québécois": le patronat québécois et les institutions universitaires, 1980-2012 - Colleret, Maxime (Revue d'histoire de l'éducation / Historical Studies in Education, 2020)
issued: 2020-21-00
Keywords: Chambre de commerce

La fonction sociale de l'université selon le patronat québécois, 1949-2012 - Colleret, Maxime (Université du Québec à Montréal, 2020)
Keywords: Chambre de commerce

GSM Project : essai historique sur une firme pionnière du design d'exposition au Québec - Cousineau, Sarah (Université du Québec à Montréal, 2020)
Keywords: Expositions

Futur parc sur la rue Marcel-Pepin. Un lieu riche en histoire - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2020)
Number: 1
Keywords: Chemins de fer; Hôpitaux; Itinérance; Usines Angus; Variole; Épidémies

GUYON, LOUIS - Dionne, Jean-Claude (Dictionnaire biographique du Canada, 2020)

"Ici, c'est le salon du peuple!" : microbrasseries, bières artisanales et communautés de consommation au Québec - Francoeur, Iannick (Université Laval, 2020)
Keywords: Brasserie; Molson (brasserie); National Breweries Limited

Le rôle méconnu des promesses de vente dans le processus d'urbanisation à Montréal: le cas du village de Villeray au tournant du XXe siècle - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2020)
issued: 2020-23-00
Keywords: Villages; Villeray

À qui la fortune sourit. La banque de Montréal et l'essor financier de l'Amérique du Nord. Volume 1. Un Dominion et des capitaux, 1817-1945 - Mussio, Laurence B. (McGill-Queen's University Press, 2020)
Keywords: Banque de Montréal; Banques

À qui la fortune sourit. La banque de Montréal et l'essor financier de l'Amérique du Nord. Volume 2. Domaines en mutation, 1946-2017 - Mussio, Laurence B. (McGill-Queen's University Press, 2020)
Keywords: Banque de Montréal; Banques

Whom fortune favours: the Bank of Montreal and the rise of North American finance. Volume 1. A Dominion of capital, 1817-1945 - Mussio, Laurence B. (McGill-Queen's University Press, 2020)
Keywords: Banque de Montréal; Banques

Whom fortune favours: the Bank of Montreal and the rise of North American finance. Volume 2. Territories of Transformation, 1946-2017 - Mussio, Laurence B. (McGill-Queen's University Press, 2020)
Keywords: Banque de Montréal; Banques

La vie économique dans le roman québécois (1956-1983) : représentations, histoire et pratiques - Nadon, Rachel (Université de Montréal, 2020)
Keywords: Parti Pris; Roman; Travail

Colonel Edward Ashworth Whitehead, Jr. Un notable habitant de Dorval / Col. Edward Ashworth Whitehead, Jr. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2020)
Keywords: Assurance; Phoenix Assurance

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Number: 4
Keywords: Lachine (canal); Paysages

Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles) - Petitclerc, Martin; Bienvenue, Louise; Niget, David; Verbauwhede, Cory (Presses de l'Université du Québec, 2020)
Keywords: Boscoville; Chômage; Commerce de détail; Crise; Délinquance; Enfants; Groupes populaires; Magasins; Marchands; Protestants; Travail

Les conditions et les " scènes " de visibilité médiatique lesbienne et féministe: l’atelier de photographie Plessisgraphe des années 70 et 80 - Pidduck, Julianne (Recherches féministes, 2020)
Number: 2
Keywords: Femmes; Féminisme; Photographie

Réflexions autour de deux pichets commémoratifs découverts sur le site du parlement à Montréal et l’abolition des Corn Laws en 1846 - Pothier, Louise (Les Cahiers des Dix, 2020)
Number: 74
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Une amitié nécessaire: entraide et fraternité dans le champ des comic books québécois (1984-1995) - Rioux, Philippe (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 2020)
Keywords: Bande dessinée; Librairie; Magasins; Édition

Le mouvement montréalais pour la fermeture de bonne heure des commerces. Genre, classe et régulation sociale du temps à l'époque libérale (1885-1909) - Rudy, Jarrett (Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles), 2020)
Keywords: Commerce de détail; Magasins; Marchands; Travail

Seam Stress: Garment Work and Gendered Labour Struggle in 1980s Montreal - Siaw, Leona (Université Concordia, 2020)
Keywords: Femmes; Grèves; Textile

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

Les coopératives de crédit et l'entrée des immigrants juifs dans l'économie montréalaise, 1911-1945 - Taschereau, Sylvie (Le fait urbain, 2020)
Keywords: Juifs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-24-00
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies

HOMIER, JOSEPH-ARTHUR - Turner, D.J. (Dictionnaire biographique du Canada, 2020)

The Hidden Face of Consumption: Extending Credit to the Urban Masses in Montreal (1920s-40s) - Taschereau, Sylvie; Rousseau, Yvan (Canadian Historical Review, 2019)
Number: 4 Reporter: Canadian Historical Review
Keywords: Marchands; Épicerie

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 6
Keywords: Incendies; Routes; Rues

Connaissez-vous Marcelin Wilson? - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 6
Keywords: Hommes d'affaires; Parcs; Philanthropie

La première couronne montréalaise est sertie de maisons shoebox (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2019)
Number: 1
Keywords: Conservation; Logement; Patrimoine; Quartiers; Rosemont

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

LAURIN, JAMES - Auger, Jean-François (Dictionnaire biographique du Canada, 2019)

L'évolution des trains de banlieue montréalais: 170 ans de service (1847-2017) - Barrieau, Pierre (Université du Québec à Montréal, 2019)
Keywords: Chemins de fer; Gares; Transport en commun

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Leméac, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

Transmettre le savoir et une vision du Canada aux jeunes Québécois: une étude de « L’Encyclopédie de la jeunesse » (1923) de la Société Grolier de Montréal - Bernier, Kristina (Université de Sherbrooke, 2019)
Keywords: Action française (L'); Nationalisme; Édition

"C'est providentiel!". Vendre le rêve suburbain à Montréal (1950-1970) - Bérubé, Harold (Cap-aux-Diamants, 2019)
issued: 2019-24-00
Keywords: Banlieue; Publicité

" De la fiction à… la réalité – de la télévision à… Laval-des-Rapides ": Mise en récit et mise en marché du rêve suburbain à Montréal, 1950–1969 - Bérubé, Harold (Quebec Studies, 2019)
Reporter: Quebec Studies
Keywords: Banlieue; Laval-des-Rapides; Publicité

Une culture du voyage. Chronique d'une maisonnée d'Ahuntsic (1925-1945) - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 5
Keywords: Automobile; Famille

Le recours aux technologies numériques pour l'étude de contenus à caractère historique et archéologique: l'exemple du site de l'ancien marché Sainte-Anne et du Parlement de la province du Canada - Charbonneau, Nathalie; Thirion, Anna (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Archéologie; Histoire; Marchés; Parlement; Patrimoine; Sainte-Anne (marché)

100 ans de bus à Montréal - Clairoux, Benoît; Constantineau, Jaysen; Lacombe, Robert; Lacourse, Jean-François (Benoît Clairoux, 2019)
Keywords: Autobus; Tramways; Transport en commun

ARMSTRONG, CHARLES JOHNSTONE - Cooke, Owen A. (Dictionnaire biographique du Canada, 2019)

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; Parcs; Travail

Il sera beau, impressionnant, mais jamais construit!: Le pont Royal-Albert - Fougères, Dany (Cap-aux-Diamants, 2019)
issued: 2019-24-00
Keywords: Ponts

FORTIN, SIFROY-JOSEPH - Fougères, Dany; Gagnon, Robert (Dictionnaire biographique du Canada, 2019)

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

Notre histoire s'écrit avec vous! – 75e de la Coop HEC Montréal - Girard, Jean-Pierre (JFD Éditions, 2019)
Keywords: École des hautes études commerciales

A Lust for Power. Electrifying Montréal's Streets and Homes, 1884-1939 - Hatton-Proulx, Clarence (Université York, 2019)

A Voice of English-Montreal. The First Twenty Years of Véhicule Press, 1973-1993 - Hemond, Amy (Université McGill, 2019)
Keywords: Imprimerie; Poésie; Édition

Claude Henri-Grignon et les droites radicales françaises de l'entre-deux-guerres: influences et échanges - Hotte, Ghyslain (2019)
issued: 2019-24-00
Keywords: Grignon; Claude-Henri; Idéologies

Le pollen, de la protohistoire à l'ère industrielle. Paysage végétal et société à la pointe à Callière, Montréal, vers 1590 à 1879 - Juteau, Audrée (Université de Montréal, 2019)
Keywords: Flore; Jardins; Paysages; Pointe-à-Callière

Communauté Milton-Parc: How We Did It and How It Works Now - Kowaluk, Lucia; Piché-Burton, Carolle (Villages in cities: community land ownership, cooperative housing, and the Milton Parc story, 2019)
Keywords: Logement; Milton-Parc; Quartiers

À propos du premier plan d'urbanisme de la Ville de Montréal (1992) - Lavallée, André (ARQ - Architecture & Design Québec, 2019)
Number: 187
Keywords: Centre-ville; Rassemblement des citoyens et citoyennes de Montréal; Transport en commun

Les hommes d'affaires français à Montréal, 1870-1914 - Linteau, Paul-André (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Number: 3
Keywords: Français; Hommes d'affaires

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Contre l'immigration française au Canada? L'alliance du Consulat général et de la Chambre de commerce française à Montréal (1893-1914) - Martinetti, Brice (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Chambre de commerce française; Consulat général de France; Français

Entre rupture et transmission: les pratiques alimentaires italiennes autour du marché Jean-Talon - Masson-Labonté, Amélie; Gagnon, Marie-Anne (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Alimentation; Italiens; Jardins; Marchés

Angelina Di Bello: une grande dame de la couture - Mathieu, Jocelyne (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Confection; Vêtements

Qui était Anthony Haig Sims? / Who was Anthony Haig Sims? - Nieuwendyk, Dick (Héritage Dorval, 2019)
Keywords: Dorval; Hommes d'affaires; Maires

La Chambre de Commerce Française de Montréal: promouvoir les échanges économiques entre la France et le Canada - Poton, Didier (Études canadiennes/Canadian Studies. Revue interdisciplinaire des études canadiennes en France, 2019)
Keywords: Chambre de commerce française

The influence of urban design theories in the transformation of urban morphology: Montreal from 1956 to 2018 - Racine, François (Journal of Urban Design, 2019)
Number: 6 Reporter: Journal of Urban Design
Keywords: Logement; Quartiers

DÉCARY, ERNEST-RÉMI - Robert, Mario (Dictionnaire biographique du Canada, 2019)

Legal Persons and Asset Management Strategy: William Clendinneng and the Canada Pipe and Foundry Company - Simeone, Daniel (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Reporter: L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles
Keywords: Banque du Peuple; Banques; Fer et acier; Mouleurs

L'art de la gravure entre 1850 et 1885 et l'architecture commerciale de Montréal : le cas de John Henry Walker - Sirois, Hélène (Université du Québec à Montréal, 2019)
Keywords: Gravure; Publicité; Walker; John Henry

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

Introducing Canada to Urban Planning? Henry Vivian's Canadian Planning Tour, 1910 - Ulmer, Catherine Mary (Urban History Review / Revue d'histoire urbaine, 2019)
issued: 2019-21-00
Keywords: Logement

RUBENSTEIN, LOUIS - Vigneault, Michel (Dictionnaire biographique du Canada, 2019)

" Je me souviens " d’un domaine seigneurial à Ahuntsic - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Communautés religieuses; Domaine Saint-Sulpice; Logement; Seigneurie; Sulpiciens

Worthless Cheques and Financial Honour: Cheque Fraud and Canadian Gentlemen Officers during the First World War - Barrett, Matthew (Histoire sociale / Social History, 2018)
Number: 104
Keywords: Banque de Montréal; Banques; Criminalité

Les quatre saisons d'Ahuntsic - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Gares; Quartiers; Toponymie; Tramways; Transport en commun

L'école Sainte-Odile: au coeur du "nouveau Cartierville" - M. Sénécal, Geneviève (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Cartierville; Logement; Parcs; Quartiers; Rues

Commerces du Plateau: d'hier à aujourd'hui (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-24-00/2019-24-00
Keywords: Alimentation; Artisans; Bijouterie; Chaussure; Commerce de détail; Magasins; Mont-Royal (rue); Plateau Mont-Royal; Quartiers; Quincaillerie; Rues; Saint-Denis (rue); Saint-Laurent (rue); Épicerie

Van Horne and Friends: Collecting European Art in Montreal’s Square Mile - Brooke, Janet M. (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne et ses amis: Collectionner l’art européen dans le Mille carré de Montréal - Brooke, Janet M. (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

La gare centrale de Montréal - Bur, Justin (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Canadien National; Canadien Pacifique; Gares

Agriculture and Urban Society on the Island of Montreal - Castonguay, Stéphane (Montreal: The History of A North American City, 2018)
Keywords: Clubs; Expositions; Jardins; Lait; Marchés

La filature Hudon - Charbonneau, Réjean; Cousineau, André (D'une track à l'autre, 2018)
Number: 3
Keywords: Hochelaga (quartier); Quartiers; Textile; Travail

La brasserie Dow. Tome 1: L'ascension - Charlebois, Paul-Yvon; Daignault, Sylvain (Les Éditions GID, 2018)
Keywords: Brasserie; Dow (brasserie)

L'affiche, une présence vivante dans la ville - Choko, Marc H. (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Canadien Pacifique; Publicité; École des Beaux-Arts

Through the Mill: Girls and Women in the Quebec Cotton Textile Industry, 1881-1951 - Cuthbert Brandt, Gail (Baraka Books, 2018)
Keywords: Femmes; Grèves; Textile; Travail

La femme illustrée par Dupuis frères limitée - de Andrade, Marie-Maxime (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Dupuis Frères; Femmes; Magasins

Le centre-ville de Montréal est-il en perte de vitesse? Analyse de la localisation des services supérieurs 1996-2011 - Duquet, Benjamin (The Canadian Geographer / Le Géographe canadien, 2018)
issued: 2018-24-00
Keywords: Centre-ville; Travail

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

"Hotel Refuses Negro Nurse": Gloria Clarke Baylis and the Queen Elizabeth Hotel - Flynn, Karen (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2018)
issued: 2018-23-00
Keywords: Femmes; Hôtellerie; Infirmières; Noirs; Reine-Élizabeth (hôtel)

The Modern City: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

The Montreal Economy during the Nineteenth Century - Fougères, Dany; Labrecque, Annie-Claude (Montreal: The History of A North American City, 2018)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime

An Undivided Island: Domination at the Dawn of a New Era - Fougères, Dany; Shaffer, Valérie (Montreal: The History of A North American City, 2018)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal

Building and Reshaping the Suburban Landscape: The Role of Immigrant Communities - Germain, Annick; Rose, Damaris; Richard, Myriam (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Permanence et renouvellement des familles ouvrières: le cas du Village-aux-Oies et de la rue Forfar, 1901-1921 - Giguère, Charles-Robert (Université du Québec à Montréal, 2018)
Keywords: Famille; Locataires; Logement; Mobilité résidentielle; Villages

Obsession: Les céramiques japonaises de Sir William Van Horne - Graham, Ron (McGill-Queen's University Press, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Obsession: Sir William Van Horne's Japanese Ceramics - Graham, Ron (McGill-Queen's University Press, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

"Like a Thread of Gold". Tracing Alfred Perry's Lifelong Engagement with Montreal's Politics of Ethnic Confrontation - Horner, Dan (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Assurance; Gavazzi; Alessandro; Hôpital Douglas; Hôpitaux psychiatriques; Incendies; Parlement; Émeutes

Les défis de la sauvegarde du patrimoine à la Société d'histoire d'Ahuntsic-Cartierville - Labarussias, Jordane (Histoire Québec, 2018)
Number: 2
Keywords: Ahuntsic; Armes; Cartierville; Conservation; Femmes; Forts; Guerre; Histoire; Patrimoine; Quartiers; Sault-au-Récollet

Mount Royal: The Top of the Island - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

Montreal: A City of Contrasts - Neatby, Nicole (From Old Quebec to La Belle Province. Tourism Promotion, Travel Writing, and National Identities, 1920-1967, 2018)
Book Authors: _:n54497
Keywords: Tourisme

The New Montreal - Neatby, Nicole (From Old Quebec to La Belle Province. Tourism Promotion, Travel Writing, and National Identities, 1920-1967, 2018)
Book Authors: _:n54505
Keywords: Tourisme

Le bâtisseur de nation - Newman, Peter C. (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

The Nation Builder - Newman, Peter C. (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Parent, Lanctôt et Helbronner. Trois figures de l’économie sociale au XIXe siècle - Petitclerc, Martin (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Helbronner; Jules; Lanctôt; Médéric; Travail

Savoirs, mobilisations et construction du risque environnemental de l'automobile durant les long sixties à Montréal - Poirier, Valérie (Université du Québec à Montréal, 2018)
Keywords: Automobile; Groupes populaires; Pollution

LAPORTE, sir HORMISDAS - Poitras, Claire (Dictionnaire biographique du Canada, 2018)

L’émeute des tramways de Montréal (1955) et la mauvaise conduite des étudiants: un cas d’appropriation de l’espace urbain - Poitras, Daniel (Urban History Review / Revue d'histoire urbaine, 2018)
issued: 2018-23-00/2019-21-00
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Délinquance; Tramways; Transport en commun; Université McGill; Université de Montréal; Émeutes; Étudiants

Montreal's Economy since 1930 - Polèse, Mario (Montreal: The History of A North American City, 2018)
Keywords: Anglophones; Aéroport; Chemins de fer; Crise; Francophones; Voie maritime

Shelter from the Hurry? Hospitality in Montreal, 1836-1913 - Poutanen, Mary Anne; Olson, Sherry (Architectures of Hurry - Mobilities and Modernity in Urban Environments, 2018)
Reporter: Architectures of Hurry - Mobilities and Modernity in Urban Environments
Keywords: Auberges; Femmes; Hôtellerie

Guerre ou pas, j'irai danser la veille du jour de l'an. Chroniques d'une danseuse invétérée - Roquigny, Peggy (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Cabarets; Danse; Publicité

Metropolitan Expansion: The Challenge of Polycentricity - Sénécal, Gilles; Vachon, Nathalie (Montreal: The History of A North American City, 2018)
Keywords: Autoroutes; Banlieue; Centres commerciaux; Mobilité résidentielle; Métropole

Montreal, 1950-2010: The Spatial Economy Transformed - Shearmur, Richard (Montreal: The History of A North American City, 2018)
Keywords: Autoroutes; Centres commerciaux; Commerce de détail; Navettage; Travail

The First Bank Strike: Labour Relations and White-Collar Union Organizing during the Second World War - Smith, Julia (Canadian Historical Review, 2018)
Number: 4
Keywords: Banque Canadienne Nationale; Banques; Grèves

Case Studies - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Catalogue des céramiques - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Ceramics Catalogue - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Études de cas - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

La "vie sociale" de la collection de céramiques japonaises de Van Horne - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Les carnets de Van Horne - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

The “Social Life” of the Van Horne Japanese Ceramic Collection - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne’s Notebooks - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Édifice Jean-Lesage : symbole de la seconde phase de la nationalisation de l'électricité - Tanguay, Marilou (Cahier du patrimoine, 2018)
Keywords: Hydro-Québec; Montreal Light; Heat and Power; Patrimoine; Électricité

Science and Technology: The Coming of Age of a City of Knowledge - Trépanier, Michel (Montreal: The History of A North American City, 2018)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin; Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Japan Contained: The Birth of the Asian Collections at the Montreal Museum of Fine Arts - Vigo, Laura (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Le Japon contenu: La naissance des collections asiatiques au Musée des beaux-arts de Montréal - Vigo, Laura (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

La Montreal Investment Association, le Montreal Investment Trust et la seigneurie de Beauharnois (1866–1941) - LaRose, André (Canadian Historical Review, 2017)
Number: 1
Keywords: Fiducie

C'était au temps où il neigeait vraiment (Mémoire vivante, 2017)
issued: 2017/2018
Keywords: Canadien Pacifique; Chemins de fer; Gares; Hommes d'affaires; Patrimoine; Rues; Tramways; Transport en commun; Van Horne; William

L'architecture du Plateau Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
issued: 2017-23-00
Keywords: Carmélites; Communautés religieuses; Logement; Plateau Mont-Royal; Quartiers; Églises

Une note musicale! (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
issued: 2017-24-00/2018-24-00
Keywords: Chanson; Musicien; Musique

Cinquante ans de développement de la fonction résidentielle dans le Vieux-Montréal et les anciens faubourgs: quelles leçons en tirer ? - Ananian, Priscilla (Environnement Urbain / Urban Environment, 2017)
Reporter: Environnement Urbain / Urban Environment
Keywords: Faubourgs; Logement; Quartiers; Vieux-Montréal

Un autre patriotisme. Le Canada des milieux d'affaires montréalais à la fin du XIXe siècle - Bédard, Éric (Survivance: histoire et mémoire du XIXe siècle canadien-français, 2017)
Keywords: Hommes d'affaires

L'ancienne gare de triage d'Outremont: voix et perspectives - Béliveau, Johanne (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
issued: 2017-21-00
Keywords: Canadien Pacifique; Chemins de fer; Gares; Travail

Vendre la banlieue aux Montréalais: discours et stratégies publicitaires, 1950-1970 - Bérubé, Harold (Revue d'histoire de l'Amérique française, 2017)
issued: 2017-22-00/2017-23-00
Keywords: Anglophones; Banlieue; Francophones; Publicité

La gare de triage d'Outremont - Bizier, Hélène-Andrée (Mémoire vivante, 2017)
issued: 2017-22-00
Keywords: Chemins de fer; Gares; Mile End; Outremont; Quartiers

Le réseau ferroviaire du Canadien Pacifique à Montréal - Bur, Justin (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
issued: 2017-21-00
Keywords: Canadien Pacifique; Chemins de fer; Gare Viger; Gare Windsor; Gares

Nourrir le quartier, nourrir la ville - Burgess, Joanne; Giroux, Éric (Écomusée du fier monde, 2017)
Keywords: Alimentation; Biscuiterie; Boulangerie; Brasserie; Centre-sud (quartier); Magasins; Marchés; Quartiers; Épicerie

Le Quartier chinois au centre-ville de Montréal. Le processus de construction d'un quartier - Cha, Jonathan (Montréal : la cité des cités, 2017)
Keywords: Chinois; Quartier chinois; Quartiers; Tourisme

Eusèbe Senécal imprimeur-éditeur 1860-1902 - Cudia, Caroline (Université du Québec à Montréal, 2017)
Keywords: Imprimerie; Revue canadienne (La); Senécal; Eusèbe; Édition

Du bagel au yoga de luxe. Consommer un vivre-ensemble imaginé rue Saint-Viateur - Désilets, Gabrielle (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Gentrification; Mile End; Quartiers

L’autoroute Ville-Marie : vision monumentale et division sociale - Economides, Aliki; MacWhirter, Colin (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Autoroutes; Centre-ville; Drapeau; Jean; Maires; Quartiers; Voirie

La station Préfontaine, la station dans le prolongement du réseau du métro de Montréal - Fallah, Bessam (ARQ - Architecture Québec, 2017)
Number: 179
Keywords: Transport en commun

Corruption politique et clientélisme à Montréal de 1996 à 2011 : forces et dynamiques des institutions formelles et informelles à la lumière des travaux de la Commission Charbonneau - Gagné, Benoit (Université du Québec à Montréal, 2017)
Keywords: Maires

Des exceptions qui confirment les règles? L'entrepreneuriat féminin à Montréal, 1920-1980 - Gallez, Philomène (Université de Montréal, 2017)
Keywords: Chambre de commerce; Commerce de détail; Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Board of Trade; École des hautes études commerciales

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Number: 1
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-23-00
Keywords: Chemins de fer; Noirs; Petite-Bourgogne; Quartiers; Travail

Les relations ville-port selon une approche d’écologie territoriale : le cas de Montréal - Jugie, Jeanne-Hélène (Université de Montréal, 2017)
Keywords: Navigation; Pollution; Port

Approche critique des archétypes de pôles logistiques intermodaux en Amérique du Nord et de la rhétorique de leur promotion dans la région métropolitaine de Montréal - Lambert, Alexandre (Université de Montréal, 2017)
Keywords: Autoroutes; Aéroport; Chemins de fer; Port

Montréal, foyer principal des Français du Canada - Linteau, Paul-André (Transposer la France: l'immigration française au Canada (1870-1914), 2017)
Keywords: Français

Les blanchisseurs chinois de Montréal - Madokoro, Laura (Vivre ensemble à Montréal : épreuves et convivialités, 2017)
Keywords: Chinois

Artères commerciales et relations de pouvoir : le cas de la Plaza Saint-Hubert à Montréal - Montfils-Ratelle, Charlotte (Université du Québec à Montréal, 2017)
Keywords: Gentrification; Rues; Saint-Hubert (rue)

L'aventure agricole montréalaise : une géopolitique urbaine quid de tensions? - Nycz, Pascale (Université du Québec à Montréal, 2017)
Keywords: Alimentation; Arrondissements; Jardins; Plateau Mont-Royal

The Urban Horse and the Shaping of Montreal, 1840–1914 - Olson, Sherry (Animal Metropolis: Histories of Human-Animal Relations in Urban Canada, 2017)

Des Écossais à Montréal, aux XVIIIe et XIXe siècles - Ouellet, Jeannine (Histoire Québec, 2017)
Number: 1
Keywords: Fourrure; Hommes d'affaires; Marchands; Écossais

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Le Parlement du Canada-Uni à Montréal, 1843-1849: Un site archéologique exceptionnel - Pothier, Louise; Van Gijseghem, Hendrik (Revue parlementaire canadienne, 2017)
issued: 2017-24-00
Keywords: Archéologie; Marchés; Parlement; Sainte-Anne (marché)

La position des centrales syndicales et des organisations patronales à l'égard de l'immigration au Québec, de 1965 à 1995 - Provost-Turgeon, Florence (Université de Montréal, 2017)
Keywords: Chambre de commerce

Contrôler le logement, contrôler la Ville: l’intervention en matière de salubrité des logements à Montréal, 1930-1939 - Racette, Jean-Christophe (Université de Montréal, 2017)
Keywords: Crise; Logement; Pauvreté

Les syndicats internationaux dans l’industrie de la construction au Québec (1887–1930) - Rouillard, Jacques (Labour / Le travail, 2017)
issued: 2017-23-00
Keywords: Charpentiers; Confédération des syndicats nationaux; Conseil des métiers et du travail de Montréal; Fédération des travailleurs et travailleuses du Québec (FTQ); Menuisiers

Angus: ADN et mutations génétiques - St-Cyr, Pierre (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
issued: 2017-21-00
Keywords: Canadien Pacifique; Chemins de fer; Conservation; Patrimoine; Usines Angus

Crime et contrebande au Canada dans les années 1920: deuxième partie - Willis, John (Cap-aux-Diamants, 2017)
issued: 2017-24-00
Keywords: Criminalité

Remontée de Holt Renfrew rue Sherbrooke - Willis, John (Cap-aux-Diamants, 2017)
issued: 2017-21-00
Keywords: Sainte-Catherine (rue)

Rêver à pleine vitesse: l'automobile et l'idéal suburbain dans la région de Montréal entre 1945 et 1970 - Wolford, Alexandre (INRS, 2017)
Keywords: Automobile; Banlieue; Beaconsfield

Expo 67: le choix du site et la forme des îles - Legault, Réjean (ARQ - Architecture Québec, 2016)
Number: 177
Keywords: Expositions

Alimentation, commerce et patrimoine: documenter les acteurs du Vieux-Montréal victorien 1850-1880 - Burgess, Joanne (Laboratoire d'histoire et de patrimoine de Montréal, 2016)
Keywords: Alimentation; Commerce de détail; Magasins; Patrimoine; Quartiers; Vieux-Montréal

Le Plateau sur ses grands chevaux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
issued: 2016-22-00
Keywords: Chasse à courre; Chevaux; Clubs; Montreal Hunt Club; Tramways; Transport en commun

Repurposing buildings (The Westmount Historian, 2016)
Number: 2
Keywords: Conservation; Gares; Logement; Patrimoine

Tourner à droite, virer à gauche. Le Plateau politique (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
issued: 2016-21-00
Keywords: Beaubien; Louis; Bethune; Norman; Chemins de fer; Communistes; Confection; Conseillers municipaux; Députés; Femmes; Gares; Grèves; Juifs; Mile End; Médecine; Partis politiques; Plateau Mont-Royal; Quartiers; Rose; Fred; Syndicats internationaux; Travail; Union internationale des ouvriers du vêtement pour dames; Élections

GORDON, SIR CHARLES BLAIR - Brown, Robert Craig (Dictionnaire biographique du Canada, 2016)

Exploration de l'approche de la gouvernance multiniveaux : le cas de la réfection du Complexe Turcot 2007-2011 - Chauvette, Anne-Louise (Institut national de la recherche scientifique et Université du Québec à Montréal, 2016)
Keywords: Automobile; Autoroutes; Conseillers municipaux; Maires; Voirie

Apartment housing then and now: vignettes from Toronto and Montreal - Dennis, Richard (British Journal of Canadian Studies, 2016)
Number: 2
Keywords: Conservation; Logement

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

Au Vieux-Port de Montréal - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Port; Vieux-port

L'histoire des moyens de pression des employés-es des services d'entretien des entreprises de transport en commun à Montréal, 1903-2016 - Desmarais, Jacques (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2016)
issued: 2016-23-00
Keywords: Confédération des syndicats nationaux; Transport en commun

La délocalisation des emplois de services supérieurs: le cas de la RMR de Montréal 1996-2011 - Duquet, Benjamin (Université du Québec et Institut national de la recherche scientifique, 2016)
Keywords: Travail

Breaking New Ground: Montreal Mirabel International Airport, Mass Aeromobility, and Megaproject Development in 1960s and 1970s Canada - Edwards, Bret (Journal of Canadian Studies / Revue d'études canadiennes, 2016)
Number: 1
Keywords: Aéroport

Quand des parents se constituent en lobby: déficience intellectuelle et concurrence Ottawa / Québec à l'époque de l'État-Providence, 1958-1985 - Ferretti, Lucia (Bulletin d'histoire politique, 2016)
Number: 2
Keywords: Enfants

"Un nouveau chapitre de l’aviation canadienne s’ouvrira-t-il à Dorval?" – Bernard W. Sznycer, Selma G. Gottlieb et l’Intercity SG-VI - Fortier, Rénald (Histoire Québec, 2016)
Number: 3
Keywords: Avionnerie; Ingénieurs

Confitures et marinades Raymond: faites pour plaire! - Giroux, Éric (Bulletin de l'Association québécoise pour le patrimoine industriel, 2016)
issued: 2016-21-00
Keywords: Alimentation; Expositions; Musées; Écomusée du fier monde

Tragédie à LaSalle: l'explosion du 1er mars 1965 - Gravel, Denis; Boucher, Isabelle (Éditions Histoire Québec, 2016)
Keywords: Arrondissements; Incendies; LaSalle; Logement

L'ordre social dans les représentations promotionnelles de la Banque d'Épargne, diffusées sous l'égide de la Société Saint-Jean-Baptiste de Montréal entre 1924 et 1946 - Hazan, Olga (Étude d'histoire religieuse, 2016)
Number: 1-2
Keywords: Banque d'Épargne de la cité et du district de Montréal; Peinture; Publicité; Société Saint-Jean-Baptiste

La Centrale d’artisanat du Québec à Montréal - Mathieu, Jocelyne (Les Cahiers des Dix, 2016)
Number: 70
Keywords: École des Beaux-Arts; École des arts graphiques; École du meuble

A Vision Greater than Themselves. The Making of the Bank of Montreal, 1817-2017 - Mussio, Laurence B. (McGill-Queen's University Press, 2016)
Keywords: Banque de Montréal; Banques

Un destin plus grand que soi. L'histoire de la Banque de Montréal de 1817 à 2017 - Mussio, Laurence B. (McGill-Queen's University Press, 2016)
Keywords: Banque de Montréal; Banques

John Wilson McConnell. Homme d'affaires, éditeur de journal, humaniste et philanthrope canadien / John Wilson McConnell: Canadian businessman, newspaper publisher, humanitarian, and philanthropist - Nieuwendyk, Dick (Héritage Dorval, 2016)
Keywords: Hommes d'affaires; McConnell; John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

Urban Elites, Energy, and Smoke Policy in Montreal during the Interwar Period - Temby, Owen; MacFadyen, Joshua (Urban History Review / Revue d'histoire urbaine, 2016)
issued: 2016-23-00
Keywords: Montreal Board of Trade

Au coeur du monde industriel de son temps: Adrien Hébert dans le port de Montréal - Trépanier, Esther (Bulletin de l'Association québécoise pour le patrimoine industriel, 2016)
issued: 2016-23-00
Keywords: Hébert; Adrien; Peinture; Port

Crimes et contrebande aux douanes canadiennes: première partie - Willis, John (Cap-aux-Diamants, 2016)
issued: 2016-23-00
Keywords: Criminalité

Le Plateau au temps de la guerre (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-23-00
Keywords: Conscription; Femmes; Fusiliers Mont-Royal; Gares; Guerre; Houde; Camillien; Juifs; Maires; Plateau Mont-Royal; Quartiers; Roman; Tramways; Transport en commun

La tarification de l'électricité: un sujet négligé lors des débats sur la nationalisation en 1962 - Bernard, Jean-Thomas (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Hydro-Québec; Lévesque; René; Électricité; Énergie hydraulique

Silas Huntington Carpenter: un détective moderne à Montréal (1880-1912) - Busseau, Laurent (Histoire Québec, 2015)
Number: 3
Keywords: Criminalité; Police

Généalogie de l'efficacité ressentie: étude de l'évolution du rapport gestionnaire à l'efficacité ressentie dans le métro de Montréal, 1966-2014 - Carlier, Denis Julien (Université du Québec et Institut national de la recherche scientifique, 2015)
Keywords: Transport en commun

Shaping Time in the City: A Cultural History of Concrete Modernity in Montreal, 1903-2015 - Charles, Julia Morgan (Université McGill, 2015)
Keywords: Autoroutes; Béton; Port; Stade olympique

Le patrimoine de René Lévesque - Dionne-Marsolais, Rita (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Lévesque; René

Trois décisions économiques de René Lévesque - Fortin, Pierre (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Lévesque; René

Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine, 2015)
issued: 2015-23-00/2016-21-00

Le rôle des grands événements dans le développement touristique d'une destination métropolitaine: cas de la ville de Montréal 1960-1992 - Khomsi, Mohamed Reda (Université du Québec à Montréal, 2015)
Keywords: Expositions; Jeux olympiques; Tourisme

Un sentiment antijuif exploité par la publicité - Levesque, Sophie (Histoire Québec, 2015)
Number: 3
Keywords: Arcand; Adrien; Commerce de détail; Idéologies; Juifs; Magasins; Publicité

1927. Le magasin Eaton s'agrandit pour mieux vous servir! - Mathieu, Jocelyne (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Eaton; Magasins

SMART, CHARLES ALLAN - Morton, Desmond (Dictionnaire biographique du Canada, 2015)

William Zeckendorf, Place Ville-Marie, and the Making of Modern Montreal - Nerbas, Don (Urban History Review / Revue d'histoire urbaine, 2015)
issued: 2015-21-00
Keywords: Gratte-ciel; Place Ville-Marie

Branding ''the Bay/la Baie'': Corporate Identity, the Hudson's Bay Company, and the Burden of History in the 1960s - Opp, James (The Canadian Historical Review, 2015)
Number: 2
Keywords: Commerce de détail; Compagnie de la Baie d'Hudson; Magasins; Publicité

1900. Pourquoi pas un gram-o-phone Berliner? - P. Bouliane, Sandria (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Chanson; Gramophone; Musique

L'appréciation de l'action économique de René Lévesque - Paquette, Pierre (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Lévesque; René

''L'autoroute est-ouest, c'est pas le progrès!'': environnement et mobilisation citoyenne en opposition au projet d'autoroute est-ouest à Montréal en 1971 - Poirier, Valérie (Bulletin d'histoire politique, 2015)
issued: 2015-24-00
Keywords: Autoroutes; Groupes populaires

La malédiction des ressources, revue et corrigée: leçons pour le Québec - Polèse, Mario (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Lévesque; René

DROUIN, JOSEPH (baptisé Joseph-Firmin) - Pratt, Michel (Dictionnaire biographique du Canada, 2015)

La danse pour tout un chacun: pratiques différenciées d’un loisir commercial à Montréal pendant l’entre-deux-guerres - Roquigny, Peggy (Mens, 2015)
issued: 2015-23-00
Keywords: Danse

''Vive la vélorution!'': Le Monde à bicyclette et les origines du mouvement cycliste à Montréal, 1975-1980 - Ross, Daniel (Bulletin d'histoire politique, 2015)
issued: 2015-24-00
Keywords: Cyclisme; Groupes populaires

Nationalisation de l'électricité et maîtrise du développement: acteurs et effets - Sales, Arnaud (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Hydro-Québec; Lévesque; René; Électricité; Énergie hydraulique

La deuxième nationalisation de l'électricité au Québec: perspectives historiques - Savard, Stéphane (René Lévesque. Les ressources naturelles et le développement économique, 2015)
Keywords: Hydro-Québec; Lévesque; René; Électricité; Énergie hydraulique

René Lévesque. Les ressources naturelles et le développement économique - Stefanescu, Alexandre; Saint-Pierre, Céline (VLB, 2015)
Keywords: Hydro-Québec; Lévesque; René; Électricité

Why Did We Choose to Industrialize? Montreal, 1819-1849 - Sweeny, Robert (McGill-Queen's University Press, 2015)

Le métro de Montréal, élément du patrimoine moderne? - Vanlaethem, France (Bulletin de l'Association québécoise pour le patrimoine industriel, 2015)
issued: 2015-23-00
Keywords: Transport en commun

Le choix du tout-à-l'automobile (1953-1967): un contexte propice à l'aménagement de l'échangeur Turcot - Wolford, Alexandre (Université de Montréal, 2015)
Keywords: Automobile; Autoroutes; Voirie

Charities, Manufactures, and Taxes: The Montreal Sisters of Providence Spruce Gum Syrup Case, 1876-78. - Little, J. I. (Canadian Historical Review, 2014)
Number: 1
Keywords: Communautés religieuses; Produits pharmaceutiques; Soeurs de la Providence

Au temps des chevaux et des rails (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2014)
issued: 2014-22-00
Keywords: Automobile; Chemins de fer; Chevaux; Cyclisme; Funiculaire; Gares; Groupes populaires; Mont Royal; Plateau Mont-Royal; Quartiers; Tramways; Transport en commun

Le Plateau gourmand (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2014)
issued: 2014-21-00
Keywords: Alcool; Alimentation; Communautés religieuses; Institut du Bon-Conseil; Juifs; Lait; Marchés; Plateau Mont-Royal; Quartiers; Restaurant; Épicerie

Une banque dans Hochelaga - l'immeuble de la Fondation Guido Molinari (Fondation Guido Molinari, 2014)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques; Hochelaga (quartier); Quartiers

Profil économique de William Notman. Bilan des connaissances - Beaulieu, Marion (Laboratoire d'histoire et de patrimoine de Montréal, 2014)
Keywords: Notman; William; Photographie

Les cyclistes: du progrès moderne à la révolution écologiste - Carel, Ivan (De la représentation à la manifestation: groupes de pression et enjeux politiques au Québec, XIXe et XXe siècles, 2014)
Keywords: Cyclisme; Groupes populaires

Historique architectural et social du bâtiment - Déom, Claudine (Une banque dans Hochelaga - l'immeuble de la Fondation Guido Molinari, 2014)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques; Hochelaga (quartier); Quartiers

WILLIS, ALEXANDER PARKER - Gallop, Mark W. (Dictionnaire biographique du Canada, 2014)

La Commission administrative et la modernisation des structures politiques et administratives de Montréal, 1918-1921 - Gaudry, William (Université de Montréal, 2014)
Keywords: Fonctionnaires; Hôtel de ville

Penser la mobilité, penser Montréal. La planification du tracé du réseau initial de métro, 1960-1966 - Gilbert, Dale (Revue d'histoire de l'Amérique française, 2014)
issued: 2014-22-00/2014-23-00
Keywords: Transport en commun

La grève étudiante de 1978 en économie à l'UQAM: l'enjeu du pluralisme et de la réflexion critique dans la formation universitaire en économie - Gill, Louis (Bulletin d'histoire politique, 2014)
issued: 2014-21-00
Keywords: Université du Québec à Montréal; Étudiants

Analyse des processus de recherche et de modélisation du patrimoine à partir de deux cas: l'écluse Saint-Gabriel du canal de Lachine et la gare Montreal and Southern Counties Railways Co. - Gosselin, Louis Pierre (Université de Sherbrooke, 2014)
Keywords: Chemins de fer; Gares; Lachine (canal); Navigation; Patrimoine

LEVINSON, SOLOMON - Lapidus, Steven (Dictionnaire biographique du Canada, 2014)

Une vie de débardeur: luttes syndicales au port de Montréal, 1960-1975 - Martel, Étienne (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2014)
issued: 2014-21-00
Keywords: Port

Une vie de débardeur: troubles et changements au port de Montréal (1960-1975) - Martel, Étienne (Université du Québec à Montréal, 2014)
Keywords: Port

Restructuration métropolitaine à Montréal entre 1998 et 2008: l'évolution des liens entre le lieu de résidence et le lieu d'emploi - Poulin, Pier-Olivier (Université du Québec et Institut national de la recherche scientifique, 2014)
Keywords: Automobile; Navettage; Transport en commun; Travail

Quartiers durables et pôles d'emploi: vers des navettes plus courtes et moins polluantes? Une analyse de Montréal, 1998-2008 - Poulin, Pier-Olivier; Shearmur, Richard (Cahiers de géographie du Québec, 2014)
Number: 163
Keywords: Navettage

L’ère des archives québécoises sur le Web - Robert, Mario (Cap-aux-Diamants, 2014)
issued: 2014-24-00
Keywords: Archives; Archives municipales

Émergence et évolution d’une profession artistique: les dessinateurs de presse entre 1880 et 1914 à Montréal - Danaux, Stéphanie (Médias 19, 2013)
Keywords: Caricature; Gravure; Patrie (La)

Quand les Pointeliers cultivaient leurs champs: une brève histoire de l'agriculture à la Pointe-aux-Trembles - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2013)
Keywords: Pointe-aux-Trembles

Seigneurs and Landowners: An Ecclesiastical Economic Vision - Dickinson, John A. (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46695
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Mise en scène de l'ethnicité? Les commerces sud-asiatiques de Parc-Extension: leur façade et leur commerçant - Dufresne, Marie-Ève (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2013)
Keywords: Commerce de détail; Parc-Extension (quartier); Quartiers

Esthétique de la typographie: Roland Giguère, les Éditions Erta et l'École des arts graphiques - Dulude, Sébastien (Nota Bene, 2013)
Keywords: École des arts graphiques; Édition

Vehicle-Pedestrian Accidents at Signalized Intersections in Montréal - Fernandes, David (Université McGill, 2013)
Keywords: Rues

''Run'' de lait: le laitier et la bouteille - Giroux, Éric (Gastronomie québécoise et patrimoine, 2013)
Keywords: Lait; Musées

Falling Up and Staying High: Commute Transit Mode Share Trends in Montreal Age Groups and Birth Cohorts - Grimsrud, Michael (Université McGill, 2013)
Keywords: Transport en commun

The Effects of Urban Rapid Rail Transit on Gentrification in Canadian Urban Centres - Grube-Cavers, C. Annelise (Université Concordia, 2013)
Keywords: Gentrification; Tramways

Can Transit and Spatial Planning Synergy Work at the Regional Scale? Understanding Metropolitan Transit-Oriented Development Planning and its Challenges in the Canadian City-Regions of Toronto, Montreal and Vancouver - Hamzah, Muhammad Zulkarnain (Université McGill, 2013)
Keywords: Transport en commun

Household Activity Spaces and Neighborhood Typologies: A Spatial and Temporal Comparative Analysis of the Effects of Clustered Land Use Indicators on the Travel Behaviour of Households in Three Quebec cities - Harding, Christopher (Université Concordia, 2013)
Keywords: Transport en commun

Montreal Electric Streetcar Suburbanization: A Study of a Canadian City’s Morphological Transformation Before World War 1 - Karczmar, Christine Elizabeth (Université McGill, 2013)
Keywords: Banlieue; Tramways

À travers le pare-brise: la création des territoires touristiques à l’ère de l’automobile (Québec et Ontario, 1920-1967) - Lambert, Maude-Emmanuelle (Université de Montréal, 2013)
Keywords: Automobile; Tourisme

Une plongée vertigineuse dans l'histoire sociale de l'île de Montréal. Autour de la maison Brignon-Lapierre - Lapierre, Michel (Montréal en tête, 2013)
Number: 64
Keywords: Brignon-Lapierre (famille); Rébellions

Montreal's First Railway - Leduc, Michael (Michael Leduc, 2013)
Keywords: Canadien Pacifique; Chemins de fer

Les guides touristiques d’hôtels montréalais, 1857-1917 – Une stratégie publicitaire - Lefebvre, Michèle (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Publicité; Tourisme

Une vie de débardeur: troubles et changements au port de Montréal (1960-1975) - Martel, Étienne (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2013)
issued: 2013-23-00
Keywords: Port

MUIR, JAMES - McDowall, Duncan (Dictionnaire biographique du Canada, 2013)

La revue de la Chambre de commerce de Montréal et la modernisation de la métropole dans les années 1950 et 1960 - Morena, Justin Michael (Université de Montréal, 2013)
Keywords: Chambre de commerce; Métropole

GRAHAM, HUGH, 1er baron ATHOLSTAN - Raudsepp, Enn (Dictionnaire biographique du Canada, 2013)

Hydro-Québec et l'État québécois, 1944-2005 - Savard, Stéphane (Septentrion, 2013)
Keywords: Hydro-Québec; Électricité; Énergie hydraulique

Murine et Listerine: la santé et la beauté comme arguments de vente dans les publicités commerciales au Québec, 1925-1950 - Sills, Myriam (Université de Montréal, 2013)
Keywords: Publicité

Reconstruction des technologies de production métallique employées par les artisans européens et amérindiens du XVIe au XVIIIe siècle au Canada - Treyvaud, Geneviève (Université Laval, 2013)
Keywords: Archéologie; Autochtones; Britanniques; Français

Making Co-opville: Layers of Activism in Point St-Charles (1983-1992) - Vickers, Simon (Université Concordia, 2013)
Keywords: Groupes populaires; Pointe-Saint-Charles; Quartiers

La Société canadienne de science économique, une cinquantenaire à la croisée des chemins: 1960-2010 - Dupré, Ruth (L'Actualité économique, 2012)
Number: 1

Pointe-Saint-Charles: histoire de locomotives - Bélisle, Jean (Bulletin de l'Association québécoise pour le patrimoine industriel, 2012)
issued: 2012-21-00
Keywords: Canadien National; Chemins de fer; Grand Tronc

Les réseaux des «lyriques» et des «veillées»: une histoire de la chanson au Québec dans l'entre-deux-guerres par la radiodiffusion au poste CKAC de Montréal (1922-1939) - Bellemare, Luc (Université Laval, 2012)
Keywords: CKAC; Chanson; Radio

Le système régional d’innovation de l’aéronautique à Montréal: entre dynamiques territoriales et sectorielles - Ben Hassen, Tarek (Université du Québec à Montréal, 2012)
Keywords: Avionnerie

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

Agriculture et société urbaine sur l'île de Montréal - Castonguay, Stéphane (Histoire de Montréal et de sa région, 2012)
Keywords: Clubs; Expositions; Jardins; Lait; Marchés

Le tronçon de l'autoroute 25 et l'étalement urbain - Chahboub, Kamal (Université du Québec à Montréal, 2012)
Keywords: Autoroutes

Desjardins. Caisse Préfontaine-Hochelaga. 1912-2012: 100 ans ouvert sur notre monde. - Charbonneau, Réjean; Genest, Claude; Maheux, Pierre-Olivier; Bizier, Louise (Desjardins, 2012)
Keywords: Banques; Caisses populaire; Desjardins; Alphonse; Hochelaga (quartier); Quartiers

Les sources de la responsabilité du transporteur aérien international: entre conflit et complémentarité: la Convention de Montréal et son interaction avec le droit européen et national - Chassot, Laurent (Éditions Schulthess, 2012)
Keywords: Aéroport

Networks and Place in Montreal's Independent Music Industry - Cummins-Russell, Thomas A.; Rantisi, Norma M. (The Canadian Geographer / Le Géographe canadien, 2012)
issued: 2012-21-00
Keywords: Musique

Le centre commercial de l’île de Montréal: Typologie d’un espace commercial en construction, 1950-1955 - Dalcourt, Annie-Claude (Université du Québec à Montréal, 2012)
Keywords: Banlieue; Centres commerciaux; Magasins

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

"La lutte contre l'accident". Risque et accidents dans un contexte de modernité industrielle - Fahrni, Magda (Pour une histoire du risque: Québec, France, Belgique, 2012)

La ville moderne, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Une île sans partage: la domination de Montréal à l'ère d'une nouvelle dynamique insulaire - Fougères, Dany; Shaffer, Valérie (Histoire de Montréal et de sa région, 2012)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal

Potential of Built Environment Interventions Involving Deployment of Public Bicycles to Increase Utilitarian Cycling: the Case of BIXI in Montreal, Quebec - Fuller, Daniel L. (Université de Montréal, 2012)
Keywords: Cyclisme

Le "gros village" et la métropole. Constructions réciproques du crime, du danger et du risque à Montréal, du milieu du XIXe siècle aux années 1920 - Fyson, Donald (Pour une histoire du risque: Québec, France, Belgique, 2012)
Keywords: Assurance; Criminalité; Métropole

Sarto Desnoyers, l'homme aux tâches multiples 1904-1996 / Sarto Desnoyers, Jack of All Trades 1904-1996 - Garneau, André (Héritage Dorval, 2012)
Keywords: Chevaux; Dorval; Hockey; Maires; Palestre nationale; Pharmacie; Produits pharmaceutiques

Le Conseil des métiers et du travail à Montréal et le transport en commun, 1899-1930 - Gaudry, William (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2012)
issued: 2012-23-00
Keywords: Conseil des métiers et du travail de Montréal; Transport en commun

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Les affiches dans les rues de Montréal. 150 ans de présence - H. Choko, Marc (Publicité Sauvage. 25 ans et demi, 2012)
Keywords: Enseignes; Publicité

Publicité Sauvage. 25 ans et demi - H. Choko, Marc (Infopresse, 2012)
Keywords: Publicité

La conciliation des objectifs sociaux, économiques et écologiques d'initiatives locales d'économie sociale - Hamel, Mélanie (Université du Québec à Montréal, 2012)

L'institutionnalisation des organisations populaires: l'exemple des associations coopératives d'économie familiale, 1961-1985 - Hill-Paquin, Steven (Université du Québec à Trois-Rivières, 2012)
Keywords: Groupes populaires

Expressway Aesthetics : Montreal in the 1960s - Hodges, Margaret E. (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l'étude de l'architecture au Canada, 2012)
Number: 1
Keywords: Autoroutes

Un trésor à conserver - Jalbert, Isabelle (Publicité Sauvage. 25 ans et demi, 2012)
Keywords: Publicité

" Ferry Command – Ego Porta Mundi " - Jarry, Alain (Héritage Dorval, 2012)
Keywords: Dorval; Guerre

Implantation d'un prototype de tableau de bord de gestion à la direction de soutien à la gestion de la Fédération des coopératives d'habitation intermunicipale du Montréal Métropolitain (FECHIMM) - Koffi, Yao Kouma (École nationale d'administration publique, 2012)

L'économie montréalaise au XIXe siècle - Labrecque, Annie-Claude; Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime

Localisations métropolitaines et mobilité quotidienne: relation entre l’équilibre emploi-résidence et le navettage à Montréal - Laforest, Anick (Université de Montréal, 2012)
Keywords: Navettage

Le risque comme culture de la temporalité - Niget, David; Petitclerc, Martin (Pour une histoire du risque: Québec, France, Belgique, 2012)

L'État-providence, la société du risque et les fondements de la communauté politique - Petitclerc, Martin (Pour une histoire du risque: Québec, France, Belgique, 2012)
Keywords: Montpetit; Édouard

Montréal économique: de 1930 à nos jours. Récit d'une transition inachevée - Polèse, Mario (Histoire de Montréal et de sa région, 2012)
Keywords: Aéroport; Chemins de fer; Crise; Francophones; Langue; Voie maritime

L'expansion métropolitaine: vers une polycentricité assumée - Sénécal, Gilles; Vachon, Nathalie (Histoire de Montréal et de sa région, 2012)
Keywords: Autoroutes; Banlieue; Centres commerciaux; Mobilité résidentielle; Métropole

Montréal 1950-2010: la métamorphose de l'économie spatiale - Shearmur, Richard (Histoire de Montréal et de sa région, 2012)
Keywords: Autoroutes; Centres commerciaux; Commerce de détail; Navettage; Travail

Cyclist Injury Risk and Pollution Exposure at Urban Signalized Intersections - Strauss, Jillian (Université McGill, 2012)
Keywords: Cyclisme; Pollution

L’avènement de l’automobile au Québec: une petite Révolution tranquille au tournant du XXe siècle - Tremblay, Alex (Cap-aux-Diamants, 2012)
issued: 2012-23-00
Keywords: Automobile

Science et technologie à Montréal: la longue naissance d'une ville du savoir - Trépanier, Michel (Histoire de Montréal et de sa région, 2012)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin; Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

LES 25 ANS et demi DE PUBLICITÉ SAUVAGE - Turenne, Martine (Publicité Sauvage. 25 ans et demi, 2012)
Keywords: Publicité

Héritage Dorval 2011 (Héritage Dorval, 2011)
Keywords: Bijouterie; Chaussure; Dentistes; Hôtellerie; Magasins; Quincaillerie; Restaurant; Électricité

Corner of Victoria Avenue & Sherbrooke (The Westmount Historian, 2011)
Number: 2
Keywords: Banque Royale; Banques; Magasins; Rues; Sherbrooke (rue)

Les différents propriétaires et leur histoire (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Chapman; Joseph; Congrégation de Notre-Dame; Crawford; John; Dupuy; Zacharie; Greater Montreal Land Company; Logement; Nivard de Saint-Dizier; Marie-Anne; Nivard de Saint-Dizier; Étienne; Nivard-De-Saint-Dizier (maison); Steward Hunter; William; Verdun

Les commerces kitsch exotiques au Québec: reconnaissance et sauvegarde d'un nouveau patrimoine - Arsenault, Roxanne (Université du Québec à Montréal, 2011)
Keywords: Patrimoine

Enforcing the Right to Healthy Housing: Recourse for Montreal Tenants Facing Health and Safety Problems at Home - Auchinleck, Jennifer (Université McGill, 2011)
Keywords: Locataires; Logement

L’opération 5000/15000 logements sociaux et communautaires: Une réponse au besoin en logements des ménages immigrants récents à Montréal, le cas de Côte-des-Neiges - Bahlouli, Abdelaziz (Université de Montréal, 2011)
Keywords: Côte-des-Neiges; Logement; Quartiers

Les représentations territoriales des acteurs engagés à l'échelle métropolitaine - Beauvais, Félix (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

L'évolution du capital immobilier au centre-ville de Montréal - Bernier, Lyne (Université du Québec à Montréal, 2011)
Keywords: Centre-ville; Quartiers

Métropolisation et mobilité: essai de problématisation - Bherer, Laurence; Bourdeau, Julie-Anne; Collin, Jean-Pierre; Hamel, Pierre J.; Sénécal, Gilles (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

Significations de la récupération de nourriture pour les actrices et acteurs du marché Jean-Talon: une recherche exploratoire - Breault, Geneviève (Université du Québec à Montréal, 2011)
Keywords: Alimentation; Marchés

Les dynamiques des agricultures périurbaines autour de Montréal: défis et opportunités au service de la société métropolitaine - Bryant, Christopher R. (Panorama des régions du Québec, 2011)

Agriculture on the Montreal Plain, 1850-1950: Urban Market and Metropolitan Hinterland - Castonguay, Stéphane (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Marchés

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

Les bus de Verdun (I) - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 3
Keywords: Autobus; Quartiers; Transport en commun; Verdun

Les bus de Verdun (II) - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 4
Keywords: Autobus; Quartiers; Transport en commun; Verdun

La gouvernance métropolitaine en panne - Collin, Jean-Pierre (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

Grandeur et déclin de la pétrochimie sur le territoire historique de la Pointe-aux-Trembles et de Montréal-Est - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2011)
Keywords: Montréal-Est; Pointe-aux-Trembles; Pétrole; Quartiers

Mobilité spatiale et communauté imaginée - Desrosiers-Lauzon, Godefroy; Boudreau, Julie-Anne (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

Intervention publique sur le développement de grappes industrielles au Québec - Doloreux, David; Tremblay, Diane-Gabrielle; Klein, Juan-Luis; Dionne, Steve; Ben Hassen, Tarek (The Canadian Geographer / Le Géographe canadien, 2011)
issued: 2011-24-00

Pôles commerciaux et pratiques sociales des espaces publics: le gradient centre-périphérie - Duchesneau, Catherine (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

Les premiers immeubles d’appartements de Montréal, 1880–1914. Un nouveau type d’habitation - Huppé, Isabelle (Urban History Review / Revue d'histoire urbaine, 2011)
issued: 2011-21-00
Keywords: Logement

Les axes du développement urbain dans la région métropolitaine de Montréal - Jastremski, Kathryn; Lafortune, Marie-Ève; Collin, Jean-Pierre; Vachon, Nathalie (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

L'axe Centre-Nord - Jastremski, Kathryn; Lafortune, Marie-Ève; Gouardin, Élodie (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

Étude urbaine d'un îlot du faubourg Saint-Laurent: la confection sur la Main, 1880-1939 - Lacaille, Marie-Ève (Université du Québec à Montréal, 2011)
Keywords: Confection; Faubourgs; Juifs; Quartiers; Rues; Saint-Laurent (quartier); Saint-Laurent (rue)

Les jardins collectifs en milieu urbain: espaces d'éducation relative à l'éco-alimentation - Legault, Anne-Marie (Université du Québec à Montréal, 2011)
Keywords: Alimentation; Jardins

Les migrations pendulaires à Montréal: analyse de l'offre de service des transports collectifs - Marcouiller, Francis (Université de Montréal, 2011)
Keywords: Transport en commun

Les impacts des aménagements cyclables à même la chaussée sur la sécurité routière à Montréal - Marré, Needbool Félix (Université du Québec à Montréal, 2011)
Keywords: Cyclisme; Rues; Voirie

Évolution du lien entre le port et l’économie urbaine: le cas de Montréal - Massé, Élyse (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2011)
Keywords: Port

Le centre commercial comme pôle urbain: observations au fil de l'axe Centre-Nord - Myrand, Léa Méthé (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)
Keywords: Centres commerciaux

City Streets as Environmental Grid: The Challenge of Private Uses and Municipal Stewardship - Olson, Sherry (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Rues

Cinémas d’après-guerre - Pageau, Pierre (Continuité, 2011)
issued: 2011-22-00
Keywords: Cinéma

Les facteurs permettant la piétonisation - Pawlas, Manon (Université du Québec à Montréal, 2011)
Keywords: Rues

Tensions dans la planification. Les transports actifs au regard de la pratique communautaire - Pesche, Augustin (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

A City on the Move. The Surprising Consequences of Highways - Poitras, Claire (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Autoroutes

Le gigantisme: une caractéristique clé des lieux commerciaux de l'axe Centre-Nord - Poitras, Claire (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)
Keywords: Centres commerciaux

Pôles urbains et renversement des axes de mobilité: les représentations territoriales des planificateurs locaux - Reyburn, Stefan; Rochat, Lauren (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

When Bridges Become Barriers; Montreal and Kahnawake Mohawk Territory - Rueck, Daniel (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Autochtones; Ponts

L'attrait pour le modèle de l'enclave résidentielle sécurisée dans la région montréalaise. que nous révèle le discours publicitaire sur le logement neuf? - Séguin, Anne-Marie (Cahiers de géographie du Québec, 2011)
Number: 154
Keywords: Logement

Des pôles aux scènes urbaines: introduction à un projet de recherche - Sénécal, Gilles (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)
Keywords: Mobilité résidentielle; Métropole; Navettage; Quartiers; Routes

L'espace-temps métropolitain. Forme et représentations de la région de Montréal - Sénécal, Gilles (Presses de l'Université Laval, 2011)

Le pouls de l'agglomération: la mobilité à l'intérieur de l'axe Centre-nord - Sénécal, Gilles; Hamel, Pierre J.; Collin, Jean-Pierre; Jastremski, Kathryn; Vachon, Nathalie; Lafortune, Marie-Ève (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)

La maison et ses dépendances - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Conservation; Patrimoine

Acteurs métropolitains et territoire vécu - Van Neste, Sophie L. (L'espace-temps métropolitain. Forme et représentations de la région de Montréal, 2011)
Keywords: Métropole

The Impact of the Urban Form on the Spatial Distribution of Commercial Activities in Montreal - Villain, Julie (Université Concordia, 2011)
Keywords: Commerce de détail; Rues

Victoria Avenue in Westmount (The Westmount Historian, 2010)
Number: 1
Keywords: Casernes; Gares; Logement; Magasins; Rues; Westmount; Épicerie

Photography as History (The Westmount Historian, 2010)
Number: 2
Keywords: Notman; William; Photographie

Les déterminants d’une grappe, définis par le modèle de Michael Porter, sont-ils présents dans la région de Montréal? "Cas des entreprises spécialisées en biotechnologie en santé humaine situées dans la région de Montréal" - Ackah Kangah Miezan, Toyo (Université du Québec à Montréal, 2010)

Les économies d’agglomération dans les villes nord-américaines: le rôle des travailleurs du haut savoir - Arbour, Sylvie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2010)
Keywords: Travail

Le moulin de Pointe-Claire, 1710-2010 / 1710-2010, The Pointe-Claire Mill - Arsenault, Claude (Société pour la sauvegarde du patrimoine de Pointe-Claire, 2010)
Keywords: Meunerie; Pointe-Claire

Le moulin à vent de Pointe-aux-Trembles - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles avec le concours de l'arrondissement Rivière-des-Prairies - Pointe-aux-Trembles de la ville de Montréal, 2010)
Keywords: Conservation; Meunerie; Patrimoine; Pointe-aux-Trembles

Éditeur de livres et de brochures - Bennett, Paul (Le Devoir: un siècle québécois, 2010)
Keywords: Devoir (Le); Édition

H. William D. Lighthall. Westmount contre la Montréal Light, Heat & Power - Bérubé, Harold (Cap-aux-Diamants, 2010)
Number: 102
Keywords: Lighthall; William Douw; Montreal Light; Heat and Power; Westmount; Électricité

Joseph Rielle (Riel). Maire de Verdun 1904-1905 - Billard, Guy (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2010)
Number: 2
Keywords: Arpenteurs; Maires; Quartiers; Verdun

Étude sur le potentiel de développement des zones industrielles en mutation dans une perspective de requalification urbaine orientée sur les transports en commun - Bissuel-Roy, Thomas (Université du Québec à Montréal, 2010)
Keywords: Transport en commun

Propriétaires et promoteurs à LaSalle: plus d'un siècle d'évolution économique - Boucher, Bruno; Gravel, Denis (Éditions Histoire Québec, 2010)
Keywords: LaSalle; Logement

La perception du risque terroriste et de ses conséquences sur la gestion de la sécurité dans le système de transport en commun de Montréal - Browne, Tara (Université de Montréal, 2010)
Keywords: Transport en commun

L'atelier des Écores (1792-1830): Une entreprise artisanale - Chagnon, Joanne (Université du Québec à Montréal, 2010)
Keywords: Artisans; Arts sacrés; Pépin; Joseph; Quévillon; Louis; Sculpture

La concertation autour du projet immobilier Porte Sainte-Marie à Montréal: le pari de la collaboration en marge du processus habituel - Cloutier, Geneviève; Sénécal, Gilles (Lien social et Politiques, 2010)
Number: 63
Keywords: Centre-sud (quartier); Logement; Quartiers

Modélisation du processus d'innovation dans quatre TPE françaises agroalimentaires à Montréal - Daguenel, Thomas (Université du Québec à Montréal, 2010)

Hôtels, tempérance et prohibition: l'alcool dans le quotidien des Pointeliers - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2010)
Keywords: Alcool; Hôtellerie; Pointe-aux-Trembles; Prohibition; Tempérance

La gouvernance et le développement économique local: liens possibles - Dextra, Hugues (Université du Québec à Chicoutimi et Université du Québec à Rimouski, 2010)
Keywords: Montréal-Nord; Quartiers

Parcourir le Vieux-Montréal: offre touristique et interprétation du patrimoine - Drouin, Martin (Le Vieux-Montréal, un "quartier de l'histoire"?, 2010)
Keywords: Patrimoine; Quartiers; Tourisme; Vieux-Montréal

Vapeur, thermoélectricité et hydroélectricité comme force motrice le long du corridor industriel du canal de Lachine, des années 1850 à la Seconde Guerre mondiale - Gelly, Alain (Université Laval, 2010)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

Le pont Jacques-Cartier - Giroux, Éric (Histoire Québec, 2010)
Number: 2
Keywords: Ponts

Deux ponts à ne pas confondre: Honoré-Mercier et Saint-Laurent - Gravel, Denis (Histoire Québec, 2010)
Number: 2
Keywords: Canadien Pacifique; Chemins de fer; Ponts

Montréal-Est, 100 ans d'histoire et de prospérité - Gravel, Denis (Société de recherche historique archiv-histo, 2010)
Keywords: Montréal-Est

The Montreal & Southern Counties Railway Company (1909-1956) - Grumley, J. R. Thomas (Histoire Québec, 2010)
Number: 1
Keywords: Chemins de fer

La production du manuel scolaire congréganiste au Québec. Le cas de l'atelier d'imprimerie des Frères des écoles chrétiennes, 1891-1918 - Laforce, Guillaume (Université Laval, 2010)
Keywords: Communautés religieuses; Frères des écoles chrétiennes; Imprimerie

Les relations entre le transport actif et l'environnement urbain: le cas d'usagers du train de banlieue de Montréal - Lapierre, Lucie (Université de Montréal, 2010)
Keywords: Transport en commun

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Angus Shop - Leduc, Michael (Michael Leduc, 2010)
Keywords: Canadien Pacifique; Chemins de fer; Usines Angus

1870: du journal d'opinion à la presse de masse, la production industrielle de l'information - Leroux, Éric (Petit musée de l'impression et Centre d'histoire de Montréal, 2010)
OCLC: 676809390
Keywords: Asselin; Olivar; Bourassa; Henri; Buies; Arthur; Devoir (Le); Idéologies; Imprimerie; Journalistes; Lanterne (La); Lovell; John; Montreal Star; Nationalisme; Nationaliste (Le); Patrie (La); Presse (La)

La rue Sainte-Catherine: au cœur de la vie montréalaise - Linteau, Paul-André (Éditions de l'Homme et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2010)
Keywords: Rues; Sainte-Catherine (rue)

Sainte-Catherine Street: at the Heart of Montréal Life - Linteau, Paul-André (Éditions de l'Homme et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2010)
Translators: _:n42654
Keywords: Rues; Sainte-Catherine (rue)

Dossier: Histoire du meuble - Loubert, Huguette; Ouellet, Richard (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2010)
issued: 2010-24-00/2011-24-00
Keywords: Artisans; Plateau Mont-Royal; Quartiers; Sculpture; Ébénistes

Les centres d'affaires au début du XXe siècle: Montréal et les villes comparables - Mongrain, Guy; Poitras, Claire (INRS-Urbanisation, Culture et Société, 2010)
Keywords: Banques; Bourse; Centre-ville; Gratte-ciel; Hôtellerie; Logement; Quartiers

La protection du territoire agricole de la région métropolitaine de recensement (RMR) de Montréal dans un contexte d’étalement urbain - Montminy, Dominique (Université de Montréal, 2010)
Keywords: Banlieue

Les déterminants de la valeur dans le marché immobilier montréalais: étude appliquée aux lignes de distribution câblées, à la végétation et aux types de rue - Montpetit, Guillaume (Université du Québec à Montréal, 2010)
Keywords: Logement; Quartiers; Île-des-Soeurs

L’économie sociale au Québec à travers les crises structurelles et les grandes transformations (1850-2008) - Petitclerc, Martin; Lévesque, Benoît (Économie et solidarités, 2010)
Number: 2

Providing a Home and then Some: A study of Montreal's Homeownership Programme - Pinches, Brendan James (Université McGill, 2010)
Keywords: Logement

Réinvestir dans l'histoire. Trente ans de promotion immobilière dans l'arrondissement historique de Montréal - Poitras, Claire (Le Vieux-Montréal, un "quartier de l'histoire"?, 2010)
Keywords: Patrimoine; Quartiers; Vieux-Montréal

The Long, Angry Summer of ’43: labour Relations in Quebec’s Shipbuilding Industry - Pritchard, James (Labour / Le travail, 2010)
Keywords: Construction navale

Rethinking Trench Expressways: Urban Design Strategies with Applications to Montreal's Décarie Autoroute - Richer, Nadia (Université McGill, 2010)
Keywords: Autoroutes

Retour sur un projet du siècle: Hydro-Québec comme vecteur des représentations symboliques et identitaires du Québec, 1944 à 2005 - Savard, Stéphane (Université Laval, 2010)
Keywords: Hydro-Québec; Électricité; Énergie hydraulique

La prohibition - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2010)
Number: 2
Keywords: Alcool; Cabarets; Prohibition; Quartiers; Verdun

Montreal and the Megastructure, ca 1967 - Singh Riar, Inderbir (Expo 67: Not Just a Souvenir, 2010)

Instruments de politique publique en matière de réduction des émissions de gaz à effet de serre: transports urbains durables à Montréal et à Boston - Tremblay-Racicot, Fanny Rose (Université Laval, 2010)
Keywords: Transport en commun

Agriculture urbaine pour un développement durable par les jardins communautaires à Montréal: multifonctionnalité, système organisationnel et dynamique des acteurs - Wegmuller, Fabien (Université du Québec à Montréal, 2010)
Keywords: Jardins

Plutôt "s'endetter sur l'honneur". Le débat sur la loi Lacombe (1900–1903) et les origines de la société de consommation au Québec - Taschereau, Sylvie (Histoire sociale / Social History, 2009)
Number: 84

Cogentrification sociale et économique: la colocalisation de la main-d'oeuvre et des emplois de services aux entreprises à Montréal, 1996-2001 - Naud, Daniel; Apparicio, Philippe; Shearmur, Richard (Cahiers de géographie du Québec, 2009)
Plusieurs études se sont penchées sur l'évolution de la localisation des emplois de services aux entreprises. Une hypothèse qui n'a pas encore été pleinement explorée est celle selon laquelle ce secteur chercherait à s'implanter à proximité des quartiers résidentiels où réside sa main-d'oeuvre. Notre étude démontre qu'il semble effectivement y avoir une certaine colocalisation, mais que celle-ci affecte principalement la main-d'oeuvre résidant à proximité du centre-ville. Ici, on trouve que les nouveaux emplois de services aux entreprises tendent à se localiser à proximité des quartiers déjà habités par leurs employés. Ceci nous permet d'avancer l'hypothèse d'une cogentrification : d'abord résidentielle, alors que certains professionnels se sont, depuis une vingtaine d'années, réapproprié des quartiers péricentraux de Montréal. Ensuite économique, tandis que les emplois de bureau en services aux entreprises se sont localisés vers ces mêmes quartiers. Many studies are currently investigating the localization of business services jobs and its development. One hypothesis, which has been insufficiently researched to date, is that this sector tends to locate in the vicinity of residential neighbourhoods where its workforce lives. This study demonstrates that though colocalization does exist to some extent, it mainly affects workers living close to the downtown area. It has been discovered that new business services jobs tend to locate in close proximity to areas already inhabited by employees in the business services sector. We can therefore hypothesize that cogentrification is primarily residential. A number of professional workers have returned to live in Montreal's pericentral neighbourhoods over the past twenty years. Cogentrification is also economic, insofar as business services office jobs have gravitated toward these same areas during the same period.
Number: 149
Keywords: Gentrification; Quartiers; Travail

Les marchés publics de Montréal, 1830-1880. Rapport final - St-Onge, Julie (s. éd., 2009)
Keywords: Marchés

Les nouvelles dynamiques régionales de l’économie québécoise: cinq tendances - Polèse, Mario (Recherches sociographiques, 2009)
issued: 2009-01/2009-04

Perceptions et pratiques des agents de sécurité aéroportuaire - Béliveau-Verville, Julie (Université de Montréal, 2009)
Keywords: Aéroport

Des réseaux locaux aux monopoles régionaux. La régionalisation des marchés de l’électricité au Québec, 1900-1935 - Bernier, Simon (Université du Québec à Trois-Rivières, 2009)
Keywords: Électricité

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

La compagnie maritime Allan: de l'Écosse au Canada au XIXe siècle - Blondel-Loisel, Annie (L'Harmattan, 2009)
Keywords: Allan Royal Mail Line; Allan; Andrew; Allan; Hugh; Navigation

Accessibility: A Performance Measure for Land-Use and Transportation Planning in the Montréal Metropolitan Region - Cerdá, Assumpta (Université McGill, 2009)
Keywords: Navettage

L'article 29 de la convention de Montréal: clef de voûte de la responsabilité du transporteur aérien international - Chassot, Laurent (Université McGill, 2009)
Keywords: Aéroport

The Life of James Coristine: from Griffintown to the Square Mile - Coristine, Cynthia; Browness, Ian (C. Coristine et I. Browness, 2009)
Keywords: Confection; Fourrure; Marchands; Vêtements

Mainstreaming the Perception and Practice of Ethical Fashion in Montreal - Craven, Ryan John (Université Concordia, 2009)
Keywords: Vêtements

Le loup est-il dans la bergerie? Les élus, les CDEC et la réforme municipale - Dancause, Luc (La métropolisation et ses territoires, 2009)

Vers un urbanisme de créneau. Saint-Laurent dans la région métropolitaine de Montréal - Darchen, Sébastien (La métropolisation et ses territoires, 2009)
Keywords: Saint-Laurent (ville)

Château Ramezay: le passé continue - Delisle, André (Continuité, 2009)
issued: 2009-21-00
Keywords: Cartes et plans; Ramezay (château de)

Les grandes gares ferroviaires du Québec: 1888-1945 - Delli-Colli, Vittoria (Université Laval, 2009)
Keywords: Chemins de fer; Gares

Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme - Delorme, Pierre (Liber, 2009)
Keywords: Tourisme

Le développement de la presse depuis la Conquête jusqu'à l'Union - Doyon, Nova (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay; Ludger; Imprimerie; Minerve (La); Montreal Gazette; Montreal Herald

L'image de marque des grandes villes: Montréal dans le monde - Duguay, Benoit (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Publicité

Adhémar Raynault (1891-1984) - Dupont, Antonin (Il était une fois... Montréal-Nord, 2009)
issued: 2009-22-00
Keywords: Assurance; Maires

La construction du patrimoine du Canada entre reconnaissance publique et valorisation touristique: le rôle de la Commission des lieux et monuments historiques et des organismes de tourisme canadiens (1919-1956) - Dutour, Juliette (Université Laval, 2009)
Keywords: Commémoration; Patrimoine; Tourisme

Automobile, transports urbains et mutations: l’automobilisation urbaine de Québec, 1919–1939 - Faugier, Étienne (Urban History Review / Revue d'histoire urbaine, 2009)
issued: 2009-23-00
Keywords: Automobile

Staying Connected: How MacDougall Family Traditions Built a Business Over 160 Years - Ferrabee, James; St. B. Harrison, Michael (McGill-Queen's University Press, 2009)
Keywords: Fiducie; Hommes d'affaires

L'accession à la propriété des jeunes familles à Montréal - Geoffroy, Caroline (École nationale d'administration publique, 2009)
Keywords: Logement

The Machine in the Garden - Gibson, Andrew (Université Concordia, 2009)
Keywords: Automobile; Autoroutes; Banlieue

Commerces du coin - Giroux, Éric (Écomusée du fier monde et arrondissement Ville-Marie, 2009)
Keywords: Commerce de détail; Magasins; Quartiers; Sainte-Marie

Montréal, ville touristique accessible? - Jolin, Louis; Sarrasin, Bruno (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Tourisme

Vers une nouvelle culture de la mobilité urbaine durable - Junca-Adenot, Florence (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)

Le tourisme montréalais: un reflet de l'urbanité métropolitaine - Kadri, Boualem (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Tourisme

Évaluation du processus de consultation publique sur le Plan de transport de la Ville de Montréal - L'Allier, Simon (Université Laval, 2009)
Keywords: Transport en commun

L’industrie et l’espace urbain. Étude de l’évolution physique du site de la compagnie Dominion Glass, avenue De Lorimier, à Montréal, 1878-1947 - Lampron, Amélie (Université du Québec à Montréal, 2009)
Keywords: Dominion Glass Company

Rising to the Occasion: How Transportation Green Taxes Could Yield Double-Dividends for Montreal and the Province of Quebec - Lefebvre, Jean-François; Tanguay, Georges A.; Junca-Adenot, Florence (Critical Issues in Environmental Taxation. International and Comparative Perspectives, 2009)

Montréal: oasis gastronomique ou capitale culinaire? - Lemasson, Jean-Pierre (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Alimentation; Restaurant

Investir, construire et habiter le monde. Les 25 ans de SITQ, histoire et perspectives - Marchand, Sarah; Linteau, Paul-André (Boréal, 2009)

L'impact de la congestion routière sur l'industrie du camionnage dans la région de Montréal - Moustakbal, Ayoub (Université du Québec à Montréal, 2009)

Angus, du grand capital à l’économie sociale - Nadeau, Gaétan (Fides, 2009)
Keywords: Canadien Pacifique; Chemins de fer; Travail; Usines Angus

One (Wo)man’s Shopping is the Same (Wo)man’s history? Immigration, Advertisement and Consumption Patterns in the Greek community of Montreal 1960s-1970s - Pabst, Stavroula (Études canadiennes / Canadian Studies, 2009)
Number: 1
Keywords: Femmes; Grecs; Publicité

Une question de justice? Réforme assurancielle et tradition mutualiste au Québec (1890-1910) - Petitclerc, Martin (Revue internationale de l'économie sociale, 2009)
Number: 311
Keywords: Assurance; Travail

Embellie financière et fiscale à Montréal: complexité des nouveaux enjeux - Pilette, Danielle (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)
Keywords: Fiscalité

Designing Sustainability for Whom? Recent Housing Development in Southwest Montreal - Poitras, Claire (Local Environment. The International Journal of Justice and Sustainability, 2009)
Number: 6
Keywords: Logement

Repenser les projets autoroutiers. Deux visions de la métropole contemporaine - Poitras, Claire (La métropolisation et ses territoires, 2009)
Keywords: Autoroutes; Métropole

Notman reçoit - Samson, Hélène (Continuité, 2009)
issued: 2009-23-00
Keywords: Notman; William; Photographie

Les TOD dans la région de Montréal: la demande et les barrières à l'offre - Schiff, Sarah (Université de Montréal, 2009)
Keywords: Transport en commun

Disputed Post-Industrial Landscapes: An Enquiry into the "Loft-Living" Cultural Model in Montréal's Saint-Henri - Tam, Edith (Université Concordia, 2009)
Keywords: Logement; Quartiers; Saint-Henri

La difficulté d'innover, handicap débilitant de l'agglomération montréalaise - Tellier, Luc-Normand (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)

Preservation of Westmount Homes built in the 1800s (The Westmount Historian, 2008)
Number: 1
Keywords: Conservation; Logement; Patrimoine; Quartiers; Westmount

Gentrification, nouvel urbanisme et évolution de la mobilité quotidienne: vers un développement plus durable? Le cas du Plateau Mont-Royal (1998-2003) - Barbonne, Rémy (Recherches sociographiques, 2008)
issued: 2008-09/2008-12
Keywords: Gentrification; Navettage; Plateau Mont-Royal; Quartiers

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Number: 2
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Bombardier: A Dream with International Reach, 1942-2008 - Bombardier inc. (Bombardier inc., 2008)
Keywords: Bombardier

Bombardier: l'internationalisation d'un rêve, 1942-2008 - Bombardier inc. (Bombardier inc., 2008)
Keywords: Bombardier

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
issued: 2008/2009
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

The Mount Royal Tunnel: Canada's First Subway. An Illustrated Story of the Construction and Operation of CN's Railway Tunnel under Montreal's Mount Royal - Clegg, Anthony (Railfare DC Books, 2008)
Keywords: Canadien National; Chemins de fer; Mont Royal; Transport en commun; Tunnels

Omer DeSerres. Trois générations créatives - DeSerres, Hélène (Éditions de l'Homme, 2008)
Keywords: Magasins

La planification des grands projets d'infrastructures routières au Québec - Desjardins, Ludwig (Renouveler l'aménagement et l'urbanisme, 2008)
Keywords: Autoroutes

L'entrée de la Pointe-aux-Trembles dans la modernité: le mouvement réformiste 1900-1930 - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Pointe-aux-Trembles; Réformistes

Charles Duquette. Maire 1924-1926 - Dupont, Antonin (Il était une fois... Montréal-Nord, 2008)
issued: 2008-24-00
Keywords: Chambre de commerce; Hommes d'affaires; Maires; Pharmacie; Produits pharmaceutiques

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

J.W. McConnell: Financier, Philanthropist, Patriot - Fong, William Jesse (McGill-Queen's University Press, 2008)
Keywords: Clubs; Hommes d'affaires; McConnell; John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Environnement bâti et transport actif scolaire: le cas des écoles de proximité de la région de Montréal - Fortin-Lacasse, Katerine (Université de Montréal, 2008)
Keywords: Automobile; Enfants; Navettage

Design, Presentation Silver and Louis-Victor Fréret (1801-1879) in London and Montreal - Fox, Ross (Material Culture Review / Revue de la culture matérielle, 2008)
Pas dans la période V car il n'est pas à Montréal avant 1867 de ce que nous (JRL) comprenons
issued: 2008-21-00
Keywords: Artisans; Sculpture

Les immeubles à appartements de l'île de Montréal, émergence et évolution d'une typologie, 1880-1914 - Huppé, Isabelle (Université du Québec à Montréal, 2008)
Keywords: Logement

Entrepreneuriat et travail dans un commerce engagé: exploration du sens et panorama des pratiques des acteurs - Jauzion, Catherine (Université du Québec à Montréal, 2008)
Keywords: Cafés; Magasins; Restaurant; Travail

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

Montreal Railway Terminals - Leduc, Michael (Michael Leduc, 2008)
Keywords: Canadien National; Canadien Pacifique; Chemins de fer; Gares

Territoire, patrimoine, quartier en développement: le cas de la zone Chabanel au centre-nord de la ville de Montréal - Mariani, Alessandra (Patrimoines: fabrique, usages et réemplois, 2008)
Keywords: Patrimoine; Quartiers

Construire un système réglementaire. L'État et l'industrie télégraphique au Canada, 1846-1916 - Mauras, Éric (Université de Montréal, 2008)

Relation spatiale entre le lieu de travail et le lieu de résidence dans les services aux entreprises: le cas de la région métropolitaine de Montréal, 1996-2001 - Naud, Daniel (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2008)
Keywords: Logement; Travail

Le paternalisme industriel et la gestion des risques sociaux au Québec. Le cas de la Montreal Tramways Company au début du XXe siècle - Petitclerc, Martin (Temps, espace et modernités: mélanges offerts à Serge Courville et Normand Séguin, 2008)
Keywords: Tramways

Co-Productions of Technology, Culture and Policy in North America's Community Wireless Networking Movement - Powell, Alison (Université Concordia, 2008)
Keywords: Internet

Représentations des immigrantes roumaines sur leurs usages d'internet en contexte d'immigration à Montréal - Regus, Oriane (Université du Québec à Montréal, 2008)
Keywords: Femmes; Internet; Roumains

Rapport sur la question du logement à Montréal; phase 2 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2008)
issued: 2008-21-00
Keywords: Locataires; Logement; Pauvreté

Portrait croisé de l’évolution des déplacements des résidents et des personnes fréquentant l’arrondissement du Plateau-Mont-Royal (1998-2003): vers un développement plus durable? - Barbonne, Rémy (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2007)
Keywords: Arrondissements; Gentrification; Navettage; Plateau Mont-Royal (arrondissement)

Le pont-tunnel Louis-Hippolyte-La-Fontaine. Une oeuvre moderne sur les traces du passé - Atelier d'histoire de la Longue-Pointe; Charbonneau, Réjean; Dugas, Philippe; Foisy, Marie-Hélène; Laferrière, Monique; Marien, Chantal (Éditions Histoire Québec, 2007)
Keywords: Ponts; Tunnels

L'autonomie financière des métropoles internationales: les cas de Lyon et de Montréal - Bachman, Peggy (Université de Sherbrooke, 2007)
Keywords: Fiscalité; Métropole

L'héritage des soeurs des Saints-Nom de Jésus et de Marie à Outremont - Beauregard, Ludger (Histoire Québec, 2007)
Number: 3
Keywords: Communautés religieuses; Outremont; Quartiers; Soeurs des Saints Noms de Jésus et de Marie

Paradoxe patrimonial: le pont-tunnel Louis-Hippolyte-La Fontaine et le village de Longue-Pointe - Cayouette-Ashby, Eve-Lyne (Bulletin de l'Association québécoise pour le patrimoine industriel, 2007)
issued: 2007-21-00
Keywords: Longue-Pointe; Ponts; Saint-François-d'Assise (paroisse)

Le Vieux-Montréal: une toute autre histoire - Chartrand, Roger (Septentrion, 2007)
Keywords: Quartiers; Vieux-Montréal

L'essor du livre illustré au Québec en relation avec les milieux artistiques et éditoriaux français: 1880-1940 - Danaux, Stéphanie (Université de Montréal et Université de Poitiers, 2007)
Keywords: Édition

Seigneurs et propriétaires: une logique ecclésiastique de l'économie - Dickinson, John A. (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Comment expliquer le déclin de Montréal comme centre de transports aériens: une question de géographie économique? - Discazeaux, Carine; Polese, Mario (The Canadian Geographer / Le Géographe canadien, 2007)
issued: 2007-21-00
Keywords: Avionnerie; Aéroport

L’École du meuble de Montréal: au-delà de l’ébénisterie - Dubois, Martin (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Ébénistes; École du meuble

La publicité de l’assurance vie au Québec: stratégies et discours (1920-1960) - Dureau, Chantale (Université du Québec à Trois-Rivières, 2007)
Keywords: Assurance; Publicité

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald; William C.; Philanthropie; Tabac; Université McGill

Réaménager la tradition - Gaudreau, Valérie (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Ébénistes; École du meuble

Une économie sur ses rails: la contribution du "6000 Saint-Denis" au développement du nord de Montréal - Laplace, Josée (Bulletin de l'Association québécoise pour le patrimoine industriel, 2007)
issued: 2007-21-00
Keywords: Montreal Street Railway Company; Patrimoine; Tramways; Transport en commun

Pointe St. Charles Shop - Leduc, Michael (Michael Leduc, 2007)
Keywords: Chemins de fer; Grand Tronc

Conditions de logement des ménages immigrants et dynamiques métropolitaines à Montréal: une analyse multiniveau exploratoire - Leloup, Xavier (Cahiers québécois de démographie, 2007)
issued: 2007-21-00
Keywords: Logement

L’art dans le métro: prochaine station: restauration - Lepage, Michèle (Continuité, 2007)
issued: 2007-22-00
Keywords: Transport en commun

Étude de cas. La formation des imprimeurs: L'École des arts graphiques de Montréal. - Leroux, Eric (Histoire du livre et de l'imprimé au Canada, vol. III (1918-1980), 2007)
Keywords: Imprimerie; École des arts graphiques

Pour le Dominion et l'Empire l'idéologie du Montreal Board of Trade 1897-1921 - Lessard, Jonathan (Université de Montréal, 2007)
Keywords: Idéologies; Montreal Board of Trade

Wine and Food / Cuisine et vins - M. Romoff, Harvey (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Alcool; Alimentation; Clubs; Restaurant; University Club; Université McGill

"Nous ne voulons pas que nos héritiers soient à la merci des tiens": famille, patrimoine et entreprise chez les Rolland, 1880-1980 - Nootens, Thierry (Revue d'histoire de l'Amérique française, 2007)
Number: 1
Keywords: Famille; Patrimoine

Le parachèvement de l'autoroute 25 entre le boulevard Henri-Bourassa, à Montréal et l'autoroute 440, à Laval: une analyse coûts-bénéfices - Paré, Valérie (École des hautes études commerciales de Montréal, 2007)
Keywords: Autoroutes; Laval

Mobilier québécois au MBAM: regards dans le temps et l’espace - Pepall, Rosalind (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Musée des Beaux-Arts; Musées

Nous protégeons l'infortune. Les origines populaires de l'économie sociale au Québec - Petitclerc, Martin (VLB, 2007)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Le bois d'œuvre et le port de Montréal, 1830-1870: une approche dendroarchéologique - Poudret-Barré, Alexandre (Université de Montréal, 2007)
Keywords: Port

Equality and Urbanism: An Inquiry on Egalitarian Ethics in Planning with a Particular Reference to the Public Consultation Policy and the Overdale Approach to Equal Land-Use Opportunities of the Montreal Citizen's Movement - Pyun, Jin-Bak (Université Concordia, 2007)
Keywords: Rassemblement des citoyens et citoyennes de Montréal

Le crédit à la consommation dans le Québec d'après-guerre: une enquête exploratoire - Rainville, Bertrand (Université du Québec à Trois-Rivières, 2007)
Keywords: Banques; Caisses populaires

Modes de vie et modes de ville, activités et déplacements quotidiens à Montréal et Lyon - Ravalet, Emmanuel (Environnement Urbain / Urban Environment, 2007)
Number: 1, a61-a76
Keywords: Navettage

Un bijou de patrimoine - Rouleau, Jocelyne (Continuité, 2007)
issued: 2007-23-00
Keywords: Bijouterie; Patrimoine

Rapport sur la question du logement à Montréal; phase 1 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2007)
issued: 2007-22-00
Keywords: Locataires; Logement; Pauvreté

La fabrication culturelle d’un cigare à Montréal au tournant du vingtième siècle - Rudy, Jarrett (Tabac et fumées: regards multidisciplinaires et indisciplinés sur le tabagisme XVe-XXe siècles, 2007)
Keywords: Tabac

Publishing in the Contact Zone: Linguistic Properties of the Book Publishing Field in Montreal - Shoumarova, Lina (Université Concordia, 2007)
Keywords: Anglophones; Francophones; Langue; Édition

L'accueil touristique virtuel: l'impact de l'internet sur les centres d'information touristique de quatre villes nord-américaines - Verner, Alix (Institut national de la recherche scientifique et Université du Québec à Montréal, 2007)
Keywords: Internet; Tourisme

Institutions commerciales de Verdun. D'hier à aujourd'hui (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Commerce de détail; Confection; Magasins; Quartiers; Quincaillerie; Verdun; Vêtements; Épicerie

Transportons-nous, jadis! Une petite histoire du transport (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-21-00
Keywords: Automobile; Lachine (canal); Navigation; Ponts; Tramways; Transport en commun

La répartition spatiale des immigrants à Montréal: apport des indices de ségrégation résidentielle - Apparicio, Philippe; Leloup, Xavier; Rivet, Philippe (Publications Immigration et Métropoles, 2006)

Production, consommation et esthétique des objets domestiques en fonte au Québec au début du XXe siècle. Le cas de trois fonderies rurales - Baillargeon, Lisa (Université du Québec à Montréal, 2006)
Le cinquième chapitre est consacré à l'étude des marchés (Les marchands, communautés religieuses et industries de Montréal et Québec étant les principaux acheteurs, je trouve pertinent de conserver l'étude ??? ) JRL –> Personnellement, je le laisse uniquement dans la commerce puisque la fabrication n'est pas à Montréal, mais uniquement la consommation et de ce que je comprends, peu ou pas sur la vie quotidienne.

Benny Farm: une vocation renouvelée - Barberese, Dino (Continuité, 2006)
issued: 2006-21-00
Keywords: Conservation; Logement; Patrimoine

Les transports collectifs accessibles à Montréal: historique, constats et perspectives - Barribeau, Pierre (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2006)
Keywords: Transport en commun

Le Drummond County Railway: 1886-1900 - Blais, Ghislain (Université Laval, 2006)
Keywords: Chemins de fer

La trajectoire de l'emploi du futur chez une cohorte de Montréalais francophones entre 1971 et 1995 - Blondeau, Hélène (Revue de l'Université de Moncton, 2006)
Number: 2
Keywords: Francophones

La Main « milendoise »: un paysage commercial en mutation - Bronson, Susan D. (Continuité, 2006)
issued: 2006-24-00/2007-24-00
Keywords: Mile End; Quartiers; Rues; Saint-Laurent (rue)

The Curious Tale of the Scots and the Fur Trade: An Historiographical Account - Bumsted, J. M. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Fourrure; Écossais

Autour de l'enseigne Five Roses: la minoterie Ogilvie, figure de proue du canal de Lachine - Cadorette, Paul-Émile (Bulletin de l'Association québécoise pour le patrimoine industriel, 2006)
issued: 2006-23-00
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie Flour Mills

At the End of the Final Line. A Brief History of Aircraft Manufacturing at Canadian Vickers and Canadair - Campbell, Patrick J. (Shoreline, 2006)
Keywords: Avionnerie; Canadair; Canadian Vickers

L’émergence d’une artère commerciale: la rue Sainte-Catherine de Montréal, 1870-1913 - Charbonneau, Daniel (Université du Québec à Montréal, 2006)
Keywords: Rues; Sainte-Catherine (rue)

Étalages, vitrines, services et nouveaux espaces. Trois grands magasins de Montréal durant les années 1920 - Comeau, Michelle (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Commerce de détail; Dupuis Frères; Eaton; Magasins; Morgan

Aspects of Scottish-Canadian Material Culture: Heart Brooches and Scottish Pottery - Dalgleish, George R. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Orfèvres; Poterie; Écossais

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

Immeubles résidentiels à Montréal: l’art du compromis - Dufaux, François (Continuité, 2006)
issued: 2006-21-00
Keywords: Logement

A Gentleman of Substance: The Life and Legacy of John Redpath (1796-1869) - Feltoe, Richard (Dundurn Press, 2006)
Keywords: Hommes d'affaires; Redpath Sugar; Redpath; John; Sucre

Urban Perspectives on CED Practice: The Montreal Experience - Fontan, Jean-Marc; Hamel, Pierre J.; Morin, Richard; Shragge, Eric (Community Economic Development: Building for Social Change, 2006)

Les grands de l’aéronautique: Canadian Vickers, Canadair, Bombardier - Fortier, Rénald (Cap-aux-Diamants, 2006)
issued: 2006-23-00
Keywords: Avionnerie; Bombardier; Canadair; Canadian Vickers

L'art du laissez-faire "juste assez" la circulation automobile à Montréal: généalogie d'un régime de gouvernement libéral avancé - Gagnon, François (Université de Montréal, 2006)
Keywords: Automobile

Le marché de la maladie. Soins hospitaliers et assurances au Québec, 1939-1961 - Guérard, François; Rousseau, Yvan (Revue d'histoire de l'Amérique française, 2006)
issued: 2006-24-00
Keywords: Assurance; Hôpitaux

La maison J. A. Gagnon - Hachey, Jean-Marie (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Magasins

Using E-Government to Strengthen Montreal's Chinese Ethnic Economy - Han, Yang (Université McGill, 2006)
Keywords: Chinois; Commerce de détail; Internet

La représentation de l'industrie dans les guides bruxellois et montréalais au tournant du 20e siècle - Kenny, Nicolas (Cahiers de la Fonderie, 2006)
Number: 34
Keywords: Fer et acier; Tourisme

L'impact de la concentration sectorielle sur le niveau des loyers des centres commerciaux régionaux et supra-régionaux: une comparaison Montréal, Québec - Lavoie, Catherine (Université Laval, 2006)
Keywords: Centres commerciaux

Sojourners in the Snow? The Scots in Business in Nineteenth-Century Canada - McCalla, Douglas (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Marchands; Écossais

Le repositionnement du centre-ville de Montréal dans la structure commerciale régionale; un examen des comportements d'achat de ses travailleurs de bureau - Mercier, Charles-Olivier (Université de Montréal, 2006)
Keywords: Centre-ville; Magasins; Quartiers

Hartland de Montarville Molson: man of honour - Molson, Karen (Firefly Books, 2006)
Keywords: Brasserie; Hommes d'affaires; Molson (famille)

Mobilité et accessibilité aux services et aux transports des femmes âgées à Montréal - Murat, Chesena (Université de Montréal, 2006)
Keywords: Automobile; Femmes; Transport en commun

The History of Canadian Business, 1867-1914 - Naylor, Robin T. (McGill-Queen's University Press, 2006)
Keywords: Banques; Chemins de fer; Marchands

Valeur hédonique des terrains à usage résidentiel unifamilial sur l'île de Montréal - Özdilek, Unsal (Université de Montréal, 2006)

Le garage Boyer 1918-1948 - La quincaillerie Boyer 1930-2006: Continuité dans la diversité / Boyer Garage 1918-1948 - Boyer Hardware 1930-2006: Continuity in Diversity - Pasquin, Michel (Héritage Dorval, 2006)
Keywords: Quincaillerie

''L’association qui crée une nouvelle famille''. L’expérience populaire de la mutualité lors de la transition à l’économie de marché - Petitclerc, Martin (Revue d'histoire de l'Amérique française, 2006)
Number: 3
Keywords: Assurance; Travail

L'agriculture soutenue par la communauté et le développement des communautés rurales en milieux périurbains: le cas de Montréal - Philibert, Vincent (Université de Montréal, 2006)

L'acquisition et le développement de connaissances interactives au sein des agences de publicité canadiennes: le cas de Diesel (Montréal), Cossette (Montréal) et Publicis (Toronto) - Provost, Catherine (École des hautes études commerciales de Montréal, 2006)
Keywords: Publicité

Évaluation de la contribution de l'agriculture urbaine communautaire montréalaise à l'amélioration du cadre de vie - Reyburn, Stefan (Institut national de la recherche scientifique et Université du Québec à Montréal, 2006)
Keywords: Alimentation; Jardins

La fabrique de pipes à fumer Henderson: inventaire archéologique sur le site Henderson-Dixon, BjFj-135, Montréal, 2005. Arrondissement Ville-Marie - Roy, Christian (Ville de Montréal, 2006)
Keywords: Artisans; Tabac

Manufacturing French Canadian Tradition: Tabac Canadien and the Construction of French-Canadian Identity, 1880-1950 - Rudy, Jarrett (Histoire sociale / Social History, 2006)
Number: 77
Keywords: Tabac

Échapper à Shylock: la Hebrew Free Loan Association of Montreal entre antisémitisme et intégration, 1911-1913 - Taschereau, Sylvie (Revue d'histoire de l'Amérique française, 2006)
issued: 2006-21-00
Keywords: Juifs

Habiter, prendre pied, s'établir. Les commerçants et manufacturiers juifs de Montréal, 1918-1930 - Taschereau, Sylvie (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Juifs

Forme urbaine, comportements de localisation et mobilité quotidienne - Vandersmissen, Marie-Hélène (Cahiers de géographie du Québec, 2006)
Number: 141

The Affordable Housing Market in Montréal: a Market Analysis and Applicability Study of Inclusionary Zoning - Wang, Yun (Université de Montréal, 2006)
Keywords: Logement

L'évolution de la productivité agricole dans la plaine de Montréal, 1852-1871. Grandes et petites exploitations dans un système familial d'agriculture - Dessureault, Christian (Histoire sociale / Social History, 2005)
Number: 76

Property Developers and the Robust Downtown: the Case of Four Major Canadian Downtowns - Charney, Igal (The Canadian Geographer / Le Géographe canadien, 2005)
Number: 3

Les sociétés de prêt juives de Montréal, 1911-1945 - Taschereau, Sylvie (Urban History Review / Revue d'histoire urbaine, 2005)
Number: 2
Keywords: Juifs

Christmastime chez Dupuis Frères - Dupuis-Leman, Josette (The Beaver, 2005)
issued: 2005-12/2006-01
Keywords: Commerce de détail; Dupuis Frères; Magasins

Le Domaine. Une belle histoire qui se poursuit... Les loisirs du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc., 2005)
Keywords: Domaine Saint-Sulpice; La Familiale; Logement

Figures du libraire au Québec - Brisson, Frédéric (Documentation et bibliothèques, 2005)
issued: 2005-04/2005-06
Keywords: Beauchemin (librairie); Librairie; Magasins

L'aéroport de Saint-Hubert, 1927-1941 - Caradot, Rémi (Éditions Histoire Québec, 2005)
Keywords: Aéroport

Le patrimoine religieux de l'arrondissement Rosemont-La Petite-Patrie, à Montréal. Un spectacle ecclésial à potentiel touristique? - Cha, Jonathan (Téoros, 2005)
issued: 2005-22-00
Keywords: Monuments; Patrimoine; Rosemont; Tourisme; Églises

Le comportement de consommation artistique et culturel des groupes francophones et anglophones à Montréal - Chatti, Amel (Université du Québec à Montréal, 2005)
Keywords: Anglophones; Francophones

HELBRONNER, JULES - de Bonville, Jean (Dictionnaire biographique du Canada, 2005)

Le poids du réseau dans, ou contre le projet urbain? L'exemple de deux projets majeurs dans la région de Montréal - Desjardins, Ludwig; Gariépy, Michel (Flux - Cahiers scientifiques internationaux Réseaux et Territoires, 2005)
Number: 60-61

Les Forget, luthiers depuis un siècle - Desjardins, Marie (Éditions au Carré, 2005)
Keywords: Artisans; Musique

Trafic aérien et économie locale en Amérique du Nord: le cas de Montréal - Discazeaux, Carine (Institut national de la recherche scientifique et Université du Québec à Montréal, 2005)
Keywords: Aéroport

Le logement traditionnel à Montréal et à Glasgow: partage et différence - Dufaux, François (Montreal-Glasgow, 2005)
Keywords: Logement

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Explorer la consommation dans une perspective historique - Fahrni, Magda (Revue d'histoire de l'Amérique française, 2005)
issued: 2005-21-00

Innovation socioterritoriale et reconversion économique: le cas de Montréal - Fontan, Jean-Marc; Klein, Juan-Luis; Tremblay, Diane-Gabrielle (L’Harmattan, 2005)

WILSON, ERASTUS WILLIAM - Gagnon, Jean-Pierre (Dictionnaire biographique du Canada, 2005)

La planification des transports et le développement durable à Montréal: quelles procédures de débat public pour quelles solutions intégrées? - Gauthier, Michèle (Flux - Cahiers scientifiques internationaux Réseaux et Territoires, 2005)
Number: 60-61

Vue sur le pont, quartier Sainte-Marie - Giroux, Éric (Ville de Montréal et Écomusée du fier monde, 2005)
Keywords: Ponts; Quartiers; Sainte-Marie

McEACHRAN, DUNCAN McNAB - Goulet, Denis; Jean, Frédéric (Dictionnaire biographique du Canada, 2005)

Planification des transports et projets de SLR à Montréal: le cas de la rue Notre-Dame - Harou, Jonathan (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2005)
Keywords: Transport en commun

SCOTT, HENRI-THOMAS - Janson, Gilles (Dictionnaire biographique du Canada, 2005)

BICKERDIKE, ROBERT - Jedwab, Jack (Dictionnaire biographique du Canada, 2005)

The Glen - Leduc, Michael (Michael Leduc, 2005)
Keywords: Canadien Pacifique; Chemins de fer; Gare Windsor; Gares

La formation professionnelle des ouvriers des métiers du livre au Québec au XXe siècle - Leroux, Éric (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2005)
issued: 2005-21-00
Keywords: Imprimerie; École des arts graphiques; École technique

Les bouteilles de verre du château de Vaudreuil: une archéologie de l'alcool à Montréal, au XVIIIe siècle - Losier, Catherine (Université de Montréal, 2005)
Keywords: Alcool; Archéologie

Entre innovation et récupération: le communautaire comme lieu de pratiques économiques alternatives - Mahfoudh, Amel (Université de Montréal, 2005)
Keywords: Pauvreté

MEREDITH, sir HENRY VINCENT - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

PEASE, EDSON LOY - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

Étude de cas. Abraham de Sola, éditeur juif dans le Montréal victorien - Menkins, Richard (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: De Sola; Abraham; Juifs

KENNEDY, sir JOHN - Millard, J. Rodney (Dictionnaire biographique du Canada, 2005)

CARRUTHERS, JAMES - Mongrain, Guy (Dictionnaire biographique du Canada, 2005)

Creating an Identity: Choosing Self-Employment in Montreal - Murray, Kristine (Université Concordia, 2005)
Keywords: Internet; Travail

Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
issued: 2005-21-00
Keywords: Eaton; Femmes; Magasins

Analyse de stratégies budgétaires des municipalités en période de resserrement budgétaire sous l'angle de facteurs structurels: villes de la région métropolitaine de Montréal - Pelletier, Hermance (Institut national de la recherche scientifique et Université du Québec à Montréal, 2005)
Keywords: Fiscalité

Mutualité, protection sociale et réformes assurantielles au Québec, 1890-1945 - Petitclerc, Martin; Rousseau, Yvan (Histoire et Sociétés. Revue européenne d'histoire sociale, 2005)
Number: 16
Keywords: Assurance

GOHIER, ÉDOUARD - Poitras, Claire (Dictionnaire biographique du Canada, 2005)

Le défi du développement de public en danse contemporaine au Québec: réflexions sur les stratégies de communication développées par le milieu - Poulin, Karine (Université du Québec à Montréal, 2005)
Keywords: Danse

ANGUS, RICHARD BLADWORTH - Reford, Alexander (Dictionnaire biographique du Canada, 2005)

STEPHEN, GEORGE, 1er baron Mount Stephen - Reford, Alexander (Dictionnaire biographique du Canada, 2005)

SHAUGHNESSY, THOMAS GEORGE, 1er baron SHAUGHNESSY - Regehr, Theodore D. (Dictionnaire biographique du Canada, 2005)

TOPLEY, WILLIAM JAMES - Rodger, Andrew (Dictionnaire biographique du Canada, 2005)

ROSS, WILLIAM GILLIES - Ross, W. Gillies (Dictionnaire biographique du Canada, 2005)

LESPÉRANCE, ZOTIQUE - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

Prestwick's Freeport and the Montreal-Mirabel Foreign Trade Zone - Rowbotham, Mark (Montreal-Glasgow, 2005)

Histoire de la raffinerie de Petro-Canada à Montréal, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

History of Petro-Canada Montreal refinery, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

DUCHARME, GUILLAUME-NARCISSE - Saint-Pierre, Jacques (Dictionnaire biographique du Canada, 2005)

L’examen des projets autoroutiers dans la région de Montréal: un espace public incertain - Sénécal, Gilles (Flux - Cahiers scientifiques internationaux Réseaux et Territoires, 2005)
Number: 60-61
Keywords: Autoroutes

Atlantic Iconography: Images of the St Lawrence-Clyde Passengers Liners of the Canadian Pacific Railway. - Stevenson, Iain (Montreal-Glasgow, 2005)
Keywords: Canadien Pacifique; Chemins de fer

"Behind the Store": Montreal Shopkeeping Families between the Wars - Taschereau, Sylvie (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Alimentation; Famille; Magasins

CHAPUT, CHARLES - Taschereau, Sylvie (Dictionnaire biographique du Canada, 2005)

VALLÉE, CHARLES-AMÉDÉE - Tremblay, Marie J. (Dictionnaire biographique du Canada, 2005)

FABIEN, CLÉOPHAS - Tremblay, Robert (Dictionnaire biographique du Canada, 2005)

Le magasin Dupuis Frères de Montréal: les transformations dans le temps et l'espace d'une institution urbaine, 1868-1978 - Turgeon, Alain (Université de Sherbrooke, 2005)
Keywords: Commerce de détail; Dupuis Frères; Magasins

KEMP, sir ALBERT EDWARD - Turley-Ewart, John A.; Brown, Craig (Dictionnaire biographique du Canada, 2005)

RICHARD, MAURICE, dit le Rocket - Vigneault, Michel (Dictionnaire biographique du Canada, 2005)

BIRKS, HENRY - Villeneuve, René (Dictionnaire biographique du Canada, 2005)

On-Site Labor Productivity Estimation Using Neural Networks - Wang, Fang (Université Concordia, 2005)
Keywords: Travail

Electronic Trading, Liquidity and Information Efficiency: Evidence from the Montreal Exchange - Wang, Kunyi (Université Concordia, 2005)
Keywords: Bourse; Prix

La participation publique à l'évaluation environnementale stratégique: identification des éléments constitutifs et proposition d'une démarche méthodologique dans le cas du transport à Montréal - Wotto, Marguerite M.-J. (Université du Québec à Montréal, 2005)
Keywords: Transport en commun

GEOFFRION, LOUIS-ÉLIE - , Yves (Dictionnaire biographique du Canada, 2005)

Évaluation de l’accessibilité à l’alimentation dans le quartier Hochelaga-Maisonneuve - Zribi, Wafa (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2005)
Keywords: Alimentation; Hochelaga (quartier); Maisonneuve (quartier); Quartiers

Intimité, mobilité et urbanité en 1978 et 2000 - Bédard, Mélanie; Fortin, Andrée (Recherches sociographiques, 2004)
issued: 2004-09/2004-12

Déclin et relance économique d'une agglomération métropolitaine. Le discours et les représentations des élites économiques à Montréal - Hamel, Pierre; Poitras, Claire (Recherches sociographiques, 2004)
issued: 2004-09/2004-12
Keywords: Hommes d'affaires; Métropole

Le Domaine. Une belle histoire qui se poursuit... La Caisse du Domaine - Archambault-Malouin, Diane; Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc., 2004)
Keywords: Banques; Caisses populaires; Desjardins; Alphonse; Domaine Saint-Sulpice; Logement

Le mouvement Slow Food à Montréal: reflet d'une nouvelle conscience alimentaire cosmopolite - Bélanger, Esther (Université Concordia, 2004)
Keywords: Alimentation

A Little on the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Fashion. A Canadian Perspective, 2004)
Keywords: Eaton; Montreal Gazette; Publicité

Émergence du réseau Internet au Québec: une approche centrée sur les acteurs - Brosseau, Benoît (Université du Québec à Montréal, 2004)
Keywords: Internet

Les magasins-entrepôts de Montréal, 1850 à 1880 : formes et fonctions commerciales. Un nouveau regard - Burgess, Joanne; Lauzon, Gilles (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Magasins

Enduring Roots: Gibb and Co. and the Nineteenth-Century Tailoring Trade in Montreal - Cariou, Gail (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Commercialisation des produits de beauté, pratiques esthétiques et représentations du corps de la femme à Montréal, 1870-1915 - Chartrand, Mélanie (Université de Montréal, 2004)
Keywords: Femmes; Publicité

Les expositions agricoles et industrielles à Montréal entre 1880 et 1884 - Constant, Jean-François (Université de Montréal, 2004)
Keywords: Expositions

L'impact de la diversité industrielle et du capital humain sur la croissance économique des villes canadiennes - David, Paul-Émile (Université du Québec à Rimouski, 2004)

"S'unir pour être plus fort": le Conseil des femmes membres de la Chambre de commerce du district de Montréal, 1956-1971 - Detellier, Élise (Université de Montréal, 2004)
Keywords: Chambre de commerce; Femmes

Le Canadien Pacifique et la transformation de l'espace est-montréalais : le cas de la gare-hôtel Viger, 1891-1901 - Duchesne, Julie (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Canadien Pacifique; Gare Viger; Gares; Hôtellerie

Fashion and Refuge: The Jane Harris Salon, Montreal, 1941-1961 - Ferrabee Sharman, Lydia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Un essor laborieux : l'électricité et le monde industriel. Les choix énergétiques des entrepises du canal de Lachine, Montréal, 1880-1920 - Gelly, Alain (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

La dynamique spatiale du marché des bureaux dans la région métropolitaine de Montréal de 1987 à 2001 - Gignac, Yannick (Université de Montréal, 2004)

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Number: 4
Keywords: Paysages; Port

La multifonctionnalité de l’espace métropolitain et le développement des activités agrotouristiques en zone périurbaine de Montréal - Granjon, Denis (Université du Montréal, 2004)
Keywords: Tourisme

Sir William Hingston 1829-1907: Montreal Mayor, Surgeon and Banker - Hustak, Alan (Price Patterson, 2004)
Keywords: Hingston; William H.; Maires; Médecine

Le Conseil des métiers et du travail de Montréal (CMTM) et la question de la municipalisation des Tramways de 1900 à 1930 - Lessard, Jonathan (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2004)
issued: 2004-23-00
Keywords: Conseil des métiers et du travail de Montréal; Tramways

A City Transformed: Manufacturing Disctricts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Manufacturing Suburbs. Building Work and Home on the Metropolitan Fringe, 2004)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Architectes et ingénieurs actifs à Montréal dans les années 1960 - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Ingénieurs

Architects and Engineers Active in Montreal in the 1960s - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Ingénieurs

Les années 60: Montréal voit grand - Lortie, André (Centre canadien d'architecture, 2004)
Keywords: Métropole

Montréal 1960; les singularités d'un archétype métropolitain - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Métropole

Montreal 1960: The Singularities of a Metropolitan Archetype - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Métropole

The 60s: Montreal Thinks Big - Lortie, André (Centre canadien d'architecture et Douglas & McIntyre Ltd, 2004)
Keywords: Métropole

Stepping out: the golden age of Montreal night clubs, 1925-1955 - Marrelli, Nancy (Véhicule Press, 2004)
Keywords: Clubs

The Development of a Mature Securities Market in Montreal - McKeagan, David (Université Concordia, 2004)

Entre globalisation et réalités locales: centres commerciaux et formes urbaines à Los Angeles, Montréal et Paris / Between Globalization and Local Realities: Shopping Centers and Urban Forms in Los Angeles, Montreal and Paris - Moretti, GianPiero (Université McGill, 2004)
Keywords: Centres commerciaux

The Association of Canadian Couturiers - Palmer, Alexandra (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Une forme d'entraide populaire: histoire des sociétés québécoises de secours mutuels au 19e siècle - Petitclerc, Martin (Université du Québec à Montréal, 2004)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

L'expression architecturale de la notion de service public dans l'insdustrie nord-américaine du téléphone avant 1940 - Poitras, Claire (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Téléphone

Le dynamisme économique de Montréal: la géographie du cycle de vie de l'innovation au Québec, 1972-1989 - Ramsay, Charles (Université de Sherbrooke, 2004)

Le commerce de l'infortune. Les premiers régimes d'assurance maladie au Québec, 1880-1939 - Rousseau, Yvan (Revue d'histoire de l'Amérique française, 2004)
Si le lancement des plans d’assurance hospitalisation de la Croix Bleue en 1942 apparaît indubitablement comme un tournant dans le développement du marché de la protection contre la maladie, des expériences avaient longuement préparé le terrain. Cet article retrace les grandes étapes de la mise en place des régimes d’assurance maladie privés au Québec, depuis la fin du XIXe siècle jusqu’à la Seconde Guerre mondiale. Il est l’occasion d’examiner trois grands contextes : 1) le développement des régimes d’indemnisation fondés sur l’allocation de prestations en espèces (ceux des entreprises commerciales comme des sociétés fraternelles) ; 2) la crise des régimes d’assurance volontaire dans l’entre-deux-guerres ; 3) les efforts déployés par les promoteurs de l’assurance libérale pour mettre au point des formules de prépaiement à l’égard des frais hospitaliers et médicaux. Dans le cadre de débats mouvementés autour de l’accès aux soins de santé, un grand défi doit alors être relevé : ouvrir les portes de l’hôpital à ceux qu’on désigne à l’époque sous le vocable de « classe moyenne ».
issued: 2004-23-00
Keywords: Assurance

Les marchés de l'assurance vie au Québec entre 1880 et 1960. Une étude de la distribution spatiale des centres de décision et de l'appropriation des revenus - Rousseau, Yvan (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Assurance

Montreal's Fashion Mile: St Catherine Street, 1890-1930 - Sifton, Elizabeth (Fashion. A Canadian Perspective, 2004)
Keywords: Rues; Sainte-Catherine (rue); Vêtements

The Mail Order Catalogue : An Achievement in Mass Distribution and Labour - Willis, John (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Commerce de détail; Magasins

Les industries à LaSalle de 1912 à 2002 - Zaïd, Omar; Zitouni, Khadoudja (Histoire Québec, 2004)
Keywords: LaSalle

August 1, 1930: Canadians Thrill to the Arrival of the First Dirigible - Mills, Sean (The Beaver, 2003)
issued: 2003-08/2003-09

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

L'Hôtel Rasco: inventaire et fouille archéologiques au site Le Royer (BjFj-53), 1998: Vieux-Montréal et faubourgs - Arkéos (Ville de Montréal, 2003)
Keywords: Archéologie; Hôtellerie

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

L'aménagement du territoire axé sur les transports en commun: le cas de la ligne de train de banlieue Montréal/Blainville - Côté, Stéphanie (Université de Montréal, 2003)
Keywords: Banlieue; Transport en commun

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

Donald Alexander Smith (1820-1914) - Dansereau, Francyne; Fulleringer, Pat (Héritage Dorval, 2003)
Number: 1
Keywords: Hommes d'affaires; Smith; Donald

L'assurance mutuelle des fabriques de Montréal: partenaire du patrimoine religieux depuis 150 ans (1853-2003) - Demers, Michel (L'Assurance mutuelle des fabriques de Montréal, 2003)
Keywords: Assurance; Incendies; Églises

La librairie Rolland, 1842-1888 - Déry, Boris (Université du Québec à Montréal, 2003)
Keywords: Librairie

Le Domaine. Une belle histoire qui se poursuit... Trois coopératives... Tout un début! - Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc, 2003)
Keywords: Chaurès-Louard; Berthe; Coopérative d'habitation de Montréal; La Familiale; Logement

Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Navigation; Énergie hydraulique

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Lachine (canal)

Les marchés de Montréal: bouillon de cultures - Dubé, Catherine (Continuité, 2003)
issued: 2003-23-00
Keywords: Marchés

Terminus ferroviaires et espace urbain: le Canadien Pacifique et la transformation de l'est de Montréal, 1870-1915 - Duchesne, Julie (Université du Québec à Montréal, 2003)
Keywords: Canadien Pacifique; Chemins de fer

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

Le syndicalisme dans le commerce de l’alimentation: le cas de la grève chez Steinberg en 1975 - Durand, Caroline (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2003)
issued: 2003-23-00
Keywords: Grèves; Steinberg; Épicerie

La maison Bagg: inventaire archéologique au site BiFj-32, 1992: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2003)
OCLC: 956636261
Keywords: Logement; Marchands

Le moulin de Pointe-aux-Trembles: survol historique et analyse du parcellaire (BjFi-5), 2001 - Ethnoscop (Ville de Montréal, 2003)
Keywords: Meunerie; Pointe-aux-Trembles; Quartiers

ROTH, IDA (Steinberg) - Fahrni, Magda (Dictionnaire biographique du Canada, 2003)

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Lachine (canal); Énergie hydraulique

L'habitation type. Évolution de l'immeuble locatif pour les quartiers ouvriers: le cas de Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Logement; Quartiers; Verdun

Canadian Equity Risk Premium, 1923-2001 - Hineson, Lucas (Université Concordia, 2003)

Syndicats et collectivités dans la gouvernance locale: une recherche exploratoire à Montréal - Klein, Juan-Luis; Fontan, Jean-Marc (Recherches sociographiques, 2003)
issued: 2003-05/2003-08
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Systèmes locaux et réseaux productifs dans la reconversion économique: le cas de Montréal - Klein, Juan-Luis; Tremblay, Diane-Gabrielle; Fontan, Jean-Marc (Géographie, Économie, Société, 2003)
Number: 1

Pointe-à-Callière: le marché, façon XVIIIe - Labrosse, Francine (Continuité, 2003)
issued: 2003-23-00
Keywords: Marchés; Musée Pointe-à-Callière; Musées

La performance de Montréal et l'économie du savoir: un changement de politique s'impose - Lapointe, Alain (HEC Montréal, Institut d'économie appliquée, 2003)

Le Royal Insurance Building: recherche archéologique au site BjFj-22, 1990: Vieux-Montréal et faubourgs - Les recherches Arkhis (Ville de Montréal, 2003)
Keywords: Assurance; Pointe-à-Callière; Royal Insurance

Montréal ou la traversée du désert - Linteau, Paul-André (Les Affaires, 2003)

Patrimoine industriel: le souffle de l’art - Lord, Denis (Continuité, 2003)
issued: 2003-21-00
Keywords: Patrimoine

After Notman: Montreal Views - A Century Apart / D'après Notman: Regards sur Montreal - Un siècle plus tard - Maciejewski, Andrzej (Firefly Books, 2003)
Translators: _:n46500
Keywords: Notman; William; Photographie

L’apport des services de proximité à la construction d’une identité de quartier: analyse de services d’économie sociale et solidaire dans trois quartiers de Montréal - Morin, Richard; Rochefort, Michel (Recherches sociographiques, 2003)
issued: 2003-05/2003-08
Keywords: Centre-sud (quartier); Hochelaga (quartier); Maisonneuve (quartier); Plateau Mont-Royal; Quartiers

La nouvelle économie à la rescousse des métropoles industrielles. Analyse comparée des stratégies publiques à Montréal et à Glasgow - Poitras, Claire (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2003)
Keywords: Métropole

Pourquoi Toronto a surclassé Montréal au sommet de la hiérarchie urbaine canadienne? L’impact des différences culturelles sur la dynamique spatiale des services supérieurs - Polèse, Mario; Sheamur, Richard (Géographie, Économie, Société, 2003)
Le système urbain canadien a subi un bouleversement important après 1960. Montréal, qui trônait depuis toujours au sommet de la hiérarchie, a été supplantée par l’éternelle seconde, Toronto. De tels renversements sont inhabituels. La destinée de Montréal paraît encore plus surprenante quand on pense qu’aux États-Unis, New York est demeurée le principal centre des affaires et de la haute finance malgré le déplacement de la population et de l’activité économique vers l’ouest (et le sud). Nous commençons par remonter brièvement le fil des événements, en écartant certaines hypothèses. Pour comprendre les décisions de localisation des services supérieurs et des fonctions de direction (exercées par les sièges sociaux), nous nous servons d’un modèle qui fait ressortir les coûts de communication et les coûts de recrutement associés aux travailleurs hautement qualifiés. Nous analysons enfin la dynamique spatiale des fonctions de direction au sein de certaines industries au Canada de 1971 à 1996.
issued: 2003-07/2003-12

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Aqueduc; Énergie hydraulique

Marchés publics et structuration spatiale du commerce à Montréal: 1870-1900 - Rousseau, Dany (Université du Québec à Montréal, 2003)
Keywords: Marchés

CATELLI, CARLO ONORATO (Charles-Honoré) - Scardellato, Gabriele (Dictionnaire biographique du Canada, 2003)

L'implantation de la galerie d'art à Montréal: le cas de W. Scott & sons, 1859-1914. Comment la révision du concept d'œuvre d'art autorisa la spécialisation du commerce d'art - Sicotte, Hélène (Université du Québec à Montréal, 2003)
Keywords: Expositions; Peinture

Exploration de l'articulation entre l'évaluation environnementale stratégique et l'étude des impacts sur l'environnement - Vallée, Lucie (Université du Québec à Montréal, 2003)

The Engineers' Engineer: Sir John Kennedy and the Port of Montreal - White, Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Ingénieurs; Port

History's Floodgate: The Lachine Canal Reopens - Gedeon, Julie (The Beaver, 2002)
issued: 2002-08/2002-09
Keywords: Lachine (canal)

Food for Thought: Community Supported Agriculture and Learning - Ambach, Michael (Université Concordia, 2002)
Keywords: Jardins

Le Domaine. Une belle histoire qui se poursuit... Les jardins du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc, 2002)
Keywords: Domaine Saint-Sulpice; Jardins

Art, technologie et métropoles: le positionnement de Montréal comme ville d'innovation dans le secteur des nouvelles technologies - Aubé, Sylvain (Université du Québec à Montréal, 2002)

Mouvements sociaux et économie sociale: un arrimage en constante reconstruction - Boucher, Jacques L. (Économie et solidarités, 2002)
Number: 2

"Tuer le taudis qui nous tuera": crise du logement et discours sur la famille montréalaise d'après-guerre (1945-1960) - Bourbeau, Amélie (Université de Montréal, 2002)
Keywords: Logement; Pauvreté

Économie coopérative et formes de connaissance: analyse de l'enracinement cognitif au fondement des représentations sociales de l'activité financière dans les caisses d'économie au Québec (1945-1996) - Brochu, Paul (Université de Montréal, 2002)

Montréal, 1870-1970: portrait de l’industrie laitière urbaine - Burgess, Joanne (Cap-aux-Diamants, 2002)
issued: 2002-23-00
Keywords: Lait

Le déclin de la maison de fond de cour à Montréal, 1880–1920 - Carey, Luc (Urban History Review / Revue d'histoire urbaine, 2002)
issued: 2002-23-00
Keywords: Logement

Montréal, une île, des ponts - Conciatori, Christine (Continuité, 2002)
issued: 2002-24-00/2003-24-00
Keywords: Ponts

La revanche du territoire: l'évolution des politiques publiques québécoises en appui aux TIC depuis 1991 - Côté, Guillaume (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2002)

Le secours mutuel en transformation: l'Alliance nationale (1892-1948) - Desaulniers, Annie (Université du Québec à Trois-Rivières, 2002)
Keywords: Assurance

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
issued: 2002-22-00
Keywords: Lachine (canal)

Le canal de Lachine: du tumulte des flots à l'essor industriel et urbain, 1860-1950 - Desloges, Yvon; Gelly, Alain (Septentrion, 2002)
Keywords: Lachine (canal); Énergie hydraulique

The Lachine Canal: Riding the Waves of Industrial and Urban Development, 1860-1950 - Desloges, Yvon; Gelly, Alain (Septentrion, 2002)
Translators: _:n6332
Keywords: Lachine (canal); Énergie hydraulique

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
issued: 2002-22-00
Keywords: Navigation; Rivière des Prairies

La diffusion des innovations dans les organisations publiques: étude de trois cas de la société de transport de la communauté urbaine de Montréal - Gagnon, Francis (Université du Québec à Montréal, 2002)
Keywords: Communauté urbaine; Transport en commun

Éduquer et vendre: la Santé par le Lait Inc. - Giroux, Éric (Cap-aux-Diamants, 2002)
issued: 2002-23-00
Keywords: Lait

L'intervention municipale dans le développement résidentiel, l'opération Habiter Montréal 1990-2001 - Gomez, Élodie (Université de Montréal, 2002)
Keywords: Logement; Évaluation foncière

Internet et les médias traditionnels: analyse du discours de La Presse et du Devoir sur l'émergence des nouvelles technologies de communication - Leray, Christian (Université du Québec à Montréal, 2002)
Keywords: Devoir (Le); Internet; Presse (La)

Making and Breaking Bread in Jewish Montreal, 1920-1940 - Lerner, Eve (Université Concordia, 2002)
Keywords: Alimentation; Boulangerie; Juifs

Les transformations dans la dynamique spatiale contemporaine du Québec - Lessard, Isabelle (Université du Québec à Chicoutimi, 2002)

Battles on the Homes Front: Montreal's Response to Federal Housing Initiatives, 1941-1947 - Lyons, Christopher M. (Université Concordia, 2002)
Keywords: Guerre; Logement

Toronto vs Montreal: The Struggle for Financial Hegemony, 1860-1875 - Masters, D.C. (The Contested Past: Reading Canada's History - Selections from the Canadian Historical Review, 2002)
Keywords: Banques; Métropole

Le transport des matières dangereuses dans l'est de Montréal: une analyse critique des projets d'investissement pour la rue Notre-Dame - Mezeguet Abellard, Jean (Université de Montréal, 2002)
Keywords: Rues

Simulation d'une approche Delphi-Internet à l'évaluation environnementale stratégique d'un plan de transport à Montréal: évaluation de la satisfaction des participants - Morin, Robert (Université du Québec à Montréal, 2002)
Keywords: Internet

Évaluation des effets du système de gestion autoroutière de Montréal sur les accidents et les délais d'intervention des services d'urgence - N'Zué, Kouadio Antoine (Université de Montréal, 2002)
Keywords: Autoroutes

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

"La riante bannière de la démocratie": les sociétés de secours mutuels québécoises au 20e siècle - Petitclerc, Martin (Assurances, 2002)
Number: 1
Keywords: Assurance; Travail

La solidarité face au marché. Quelques réflexions sur l‘histoire de la mutualité au Québec - Petitclerc, Martin (Revue internationale de l'économie sociale, 2002)
Number: 283
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Origin and Evolution of the Department Store - Tamilia, Robert D. (Université du Québec à Montréal et Centre de recherche en gestion, 2002)
Keywords: Commerce de détail; Magasins

L'occupation du sous-sol urbain et la Commission des services électriques de la Ville de Montréal: les difficultés de la coordination des acteurs individuels - Thibault, Serge (Institut national de la recherche scientifique et Université du Québec à Montréal, 2002)

La localisation intramétropolitaine des services supérieurs: analyse comparative des régions métropolitaines de Toronto, Montréal, Vancouver et Ottawa-Hull en 1996 et de leur évolution entre 1981 et 1996 - Trépanier, David (Université de Montréal, 2002)

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

The Identification of Employment Centres in Canadian Metropolitan Areas: the Example of Montreal, 1996 - Coffey, William J.; Shearmur, Richard (The Canadian Geographer / Le Géographe canadien, 2001)
Number: 3

Intermodal Freight Terminals: Locality and Industrial Linkages - McCalla, Robert J.; Slack, Brian; Comtois, Claude (The Canadian Geographer / Le Géographe canadien, 2001)
Number: 3
Keywords: Aéroport; Chemins de fer; Port

A City Transformed: Manufacturing Districts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Journal of Historical Geography, 2001)
Number: 1
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Si l'aéroport de Dorval m'était conté... / If Dorval airport could speak... (Héritage Dorval, 2001)
Number: 1
Keywords: Aéroport; Dorval

Les communautés religieuses et l'édition du manuel scolaire au Québec, 1765-1964 - Aubin, Paul (Groupe de recherche sur l'édition littéraire au Québec, 2001)
Keywords: Communautés religieuses; Enseignants; Édition

La ville, agent catalyseur de développement: le rôle des municipalités dans l’évolution de l’industrie canadienne des véhicules d’incendie, 1945-1965 - Beauvais, Suzanne (Material History Review / Revue d’histoire de la culture matérielle, 2001)
Keywords: Incendies; Pompiers

Ces machines qui chantent… - Bélisle, Jean; Cloutier, Nicole (Continuité, 2001)
issued: 2001-24-00/2002-24-00
Keywords: Musique; Radio

Analyse journalière des déterminants du volume des accidents routiers dans la région métropolitaine de Montréal, 1995-1998 - Blais, Étienne (Université de Montréal, 2001)
Keywords: Routes

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

Le métro de Montréal, 35 ans déjà - Clairoux, Benoît (Hurtubise HMH, 2001)
Keywords: Transport en commun

Une petite maison... Un grand homme: Hormidas Laporte - Cloutier, Gabrielle (Montréal en tête, 2001)
issued: 2001-21-00
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

La réorganisation du travail à la raffinerie Shell de Montréal-Est, de 1989 à 1999 - Delorme, Marie-Josée (Université de Montréal, 2001)
Keywords: Montréal-Est; Pétrole; Travail

After the Pain, Beauty Remains: Identity and Aesthetics of Body Modification in Montreal - Dermerson, Elizabeth (Université Concordia, 2001)

La montagne, capital et intérêts - Dubé, Catherine (Continuité, 2001)
issued: 2001-23-00
Keywords: Mont Royal; Mont-Royal (parc); Parcs

Dupuis Frères: le magasin du peuple: plus d'un siècle de fierté québécoise - Dupuis-Leman, Josette (Stanké, 2001)
Keywords: Commerce de détail; Dupuis Frères; Magasins

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
issued: 2001-22-00
Keywords: Navigation; Voie maritime

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

A Full Century of Monthly Canadian Stock Price Index Returns: A Review of the Fisher Hypothesis and some Anomalies - Jean, Dominic (Université Concordia, 2001)
Keywords: Prix

Entre conjoncture et fusions: l’économie de Montréal dans l’expectative - Manzagol, Claude (Québec 2002. Annuaire politique, social, économique et culturel, 2001)

North of the Colour Line: Sleeping Car Porters and the Battle Against Jim Crow on Canadian Rails, 1880-1920 - Mathieu, Sarah-Jane (Saje) (Labour / Le travail, 2001)
Keywords: Chemins de fer; Noirs; Transport en commun; Travail

Segmentation des internautes bancaires montréalais - Mehrez, Karim (Université du Québec à Montréal, 2001)
Keywords: Banques; Internet

Les pratiques de gestion dans les PME de la communauté haïtienne de Montréal - Michel, Dicarmel (École des hautes études commerciales de Montréal, 2001)
Keywords: Haïtiens

Le transport à vélo: le cas des étudiants de l'Université du Québec à Montréal - Moran, Anne-Marie (Université du Québec à Montréal, 2001)
Keywords: Cyclisme; Université du Québec à Montréal; Étudiants

La "Normandie du Nouveau Monde": la société Canada Steamship Lines, l’antimodernisme et la promotion du Québec ancien - Murton, James (Revue d'histoire de l'Amérique française, 2001)
Cette étude tend à montrer que durant les années 1930 la Canada Steamship Lines (CSL) a créé et disséminé une image du Québec comme société simple, prémoderne et rurale, dans le but d’accroître la clientèle de ses navires de croisière et de ses hôtels. On y examine les documents publicitaires de la compagnie et l’on montre qu’elle faisait aussi appel à d’autres individus pour construire cette image. L’anthropologue et folkloriste Marius Barbeau a écrit un ouvrage pour le compte de la CSL et celle-ci s’est associée au gouvernement du Québec pour promouvoir le renouveau artisanal. Ces divers acteurs partageaient la croyance antimoderne dans l’existence d’un Québécois vrai, authentique et qui constituait le coeur même de la nation : l’« Habitant ».
issued: 2001-22-00
Keywords: Navigation

Déterminants de la valeur marchande des propriétés unifamiliales sur l'île de Montréal: évaluation de masse conjuguée aux SIG - Ozdilek, Unsal (Université du Québec à Montréal, 2001)
Keywords: Évaluation foncière

Le tourisme culturel à Montréal - Rémillard, Marie-France (Université Laval, 2001)
Keywords: Tourisme

L'apport des services de proximité en matière de revitalisation socio-économique des quartiers - Rochefort, Michel (Université du Québec à Montréal, 2001)
Keywords: Quartiers

La gestion de la demande des déplacements: un examen des possibilités et des contraintes dans le cas des étudiants de l'Université de Montréal - Sévigny, Éric (Université de Montréal, 2001)
Keywords: Université de Montréal; Étudiants

L'institutionnalisation des corporations de développement économique communautaire sur l'Île de Montréal - Silvestro, Marco (Université de Montréal, 2001)

Le développement économique communautaire dans un contexte métropolitain: le cas de Montréal - Silvestro, Marco (Département d’études urbaines et touristiques de l'Université du Québec à Montréal, 2001)

De génération en génération: la transmission des savoir-faire - Simard, Cyril (Cap-aux-Diamants, 2001)
issued: 2001-21-00
Keywords: Artisans

Unilingues ou bilingues? Les Montréalais sur le marché du travail en 1901 - MacKinnon, Mary (L'Actualité économique, 2000)
Cette étude utilise un échantillon du Recensement canadien de 1901 pour estimer le taux de rendement du bilinguisme pour les hommes de langue maternelle anglaise et française à Montréal. Le bilinguisme a profité aux anglophones et aux francophones; et la prime au bilinguisme pour les deux groupes semble quelque peu supérieure à celle des années 1960. En 1901, un francophone bilingue qui savait lire et écrire gagnait en moyenne à peu près le même revenu qu’un anglophone unilingue catholique. Les anglophones protestants bilingues obtenaient les revenus moyens les plus élevés.
Number: 1
Keywords: Bilinguisme; Travail

Les publicités à succès selon le concours du Publicité-Club de Montréal - Allagui, Ilhem (Université de Montréal, 2000)
Keywords: Publicité

Impact des améliorations locatives sur la valeur d'un immeuble: le cas de Place Montréal Trust - Boilly, Jacques (Université du Québec à Montréal, 2000)
Keywords: Centres commerciaux

The Evolution of Organizational Identity: A Discursive Study - Chreim, Samia (École des hautes études commerciales de Montréal, 2000)

Bruce Price, and his Montreal Train Stations - Dandurand, Kevin (Université Concordia, 2000)
Keywords: Gare Viger; Gare Windsor; Gares

Un essai sur la pertinence de l'intervention gouvernementale: les politiques publiques en matière de transport urbain des personnes - Delisle, Sylvain (Université Concordia, 2000)

Les étapes de la science économique au Québec: démarrage, construction et maturité - Fortin, Pierre (L'Actualité économique, 2000)
Number: 1
Keywords: Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun

Equity Planning and Community Economic Development: the Case of Côte des Neiges-Notre Dame de Grâce - Jacob, Benoy (Université Concordia, 2000)
Keywords: Côte-des-Neiges; Notre-Dame-de-Grâce; Quartiers

La saga du technopôle Angus: reconversion productive et reconversion sociale - Klein, Juan-Luis; Fontan, Jean-Marc; Tremblay, Diane-Gabrielle; Bordeleau, Danièle (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Usines Angus

Montreal’s Place in the North American Economy - Kresl, Peter Karl; Proulx, Pierre-Paul (American Review of Canadian Studies, 2000)
issued: 2000-23-00

Manufacturing Montreal. The Making of an Industrial Landscape, 1850-1930 - Lewis, Robert D. (John Hopkins University Press, 2000)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal, le cas des Portugais, des Maghrébins et des Italiens - Paiement, Isabelle (Université du Québec à Montréal, 2000)
Keywords: Italiens; Maghrébins; Portugais

L'accès à la transaction immobilière: un des mécanismes du processus de ségrégation résidentielle ethnique - Paré, Sylvie (Recherches sociographiques, 2000)
Number: 3
Keywords: Logement

Rapports de pouvoir et enjeux métropolitains dans l'agglomération montréalaise, 1920-1961: les problèmes de l'organisation institutionnelle, de la planification du territoire et du transport des personnes - Pineault, Stéphane (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2000)

Élaboration d'une perspective environnementale dans le secteur de l'hydroélectricité au Québec, 1890-1939 - Plamondon, Jacinthe (Université du Québec à Trois-Rivières, 2000)
Keywords: Électricité; Énergie hydraulique

La cité au bout du fil le téléphone à Montréal de 1879 à 1930 - Poitras, Claire (Presses de l'Université de Montréal, 2000)
Keywords: Bell Canada; Téléphone

Les trains de banlieue et l'aménagement du territoire dans la région de Montréal - Quirion, Étienne (Université de Montréal, 2000)
Keywords: Banlieue; Transport en commun

Histoire de la librairie au Québec - Roy, Fernande (Leméac, 2000)
Keywords: Librairie

L'autoroute urbaine à Montréal: la cicatrice et sa réparation - Sénécal, Gilles; Archambault, Julie; Hamel, Pierre J. (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Autoroutes

Hedging Canadian Short-Term Interest Rates: The BAX Market - Siam, John J. (Université Concordia, 2000)

Housing Revitalization in Montreal: Are Condominium Conversions a Sustainable Alternative? - Swaby, Chantelle Simone (Université de Montréal, 2000)
Keywords: Logement

Nouveau regard sur les relations judéo-québécoises: le commerce comme lieu d’échanges, Montréal 1900-1940 - Taschereau, Sylvie (Juifs et Canadiens français dans la société québécoise, 2000)
Keywords: Juifs

L'impact d'un casino sur l'économie urbaine: application au Casino de Montréal - Trépanier, Fannie (École des hautes études commerciales de Montréal, 2000)
Keywords: Île Notre-Dame